Natural porphin salt and application thereof as plant growth regulator and immune resistance inducer
Patent Information
- Application Number
- CN202280099559.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-06
- Publication Date
- 2025-04-11
AI Technical Summary
Existing natural porphine salts used as plant growth regulators and immune inducers have problems with photothermal instability and inconvenience, and are difficult to dissolve and disperse, which affects their application in agriculture.
Preparation of a series of natural porphine salts, including salts of porphine compounds and chlorin compounds, through salt-forming reactions with metal ions necessary for plant nutrition to form stable water-soluble products and improve their photothermal stability and solubility .
The photothermal stability and water solubility of the porphine salt are achieved, making it convenient to prepare aqueous solutions, suitable for field use, improving plant growth regulation and immune induction effects, and enhancing crop stress resistance and yield.
Smart Images

Figure CN119816503A_ABST
Abstract
Description
Natural porphin salts and their use as plant growth regulators and immune inducers Technical Field
[0001] The invention relates to natural porphin salts and applications thereof as plant growth regulators and immune inducers, belonging to the technical field of plant growth regulators. Background Art
[0002] Chlorophyll and heme are natural porphin structures found in plants and animals. They form the basis for photosynthesis, oxygen transport, and respiration, which sustain life in plants and animals. Heme has a classic porphin structure, while chlorophyll is based on a chlorin nucleus. Compared to porphin structures, chlorins exhibit greater asymmetry and exist in more complex and diverse forms and states. Currently, various porphin products extracted and processed from natural sources are finding widespread application in a variety of fields, including chemical engineering, pharmaceuticals, food, and agriculture. For example, ferric chlorophyllin (ferric chloride chlorophyllin, CN102285992B) and hemin chloride (heme, CN10048884C) have been used as new plant growth regulators in a variety of crops, ferric chlorophyllin sodium salt and sodium / potassium chlorophyllin copper salt are used as food additives (food colorants), and sodium protoporphyrin is used as a drug for the treatment of liver cirrhosis. In addition to commercially available products, in recent years, Chinese patents CN101045730, CN102351867, CN102775416 and CN 102796108 and others disclose the preparation and properties of divalent salts such as chlorophyllin iron zinc salt (chlorophyllin iron zinc salt), chlorophyllin iron calcium salt (chlorophyllin iron calcium salt), chlorophyllin iron magnesium salt (chlorophyllin iron magnesium salt), and chlorophyllin iron manganese salt (chlorophyllin iron manganese salt); the literature (Study on reaction rate, equilibrium constant and structure of iron chlorophyllin metal salts, master's thesis, North China University of Technology 2017.03) studies the preparation of a series of chlorophyllin iron metal salts, including salt formation reaction, product structure and physicochemical properties, etc., showing that chlorophyllin iron and divalent Mg 2+ , Ca 2+ 、Mn 2+ and Zn 2+ ions form a slightly soluble / insoluble salt with a 1:1 molar ratio (K sp ≈10 -16 ~10 -18 M 2), the salt-forming reaction is fast (low activation energy ~20kJ / mol); by utilizing the difference in water solubility, the divalent metal salts of these porphine chelates can be prepared by forming precipitation from aqueous solution, among which the water-soluble porphine sodium salt is the basic raw material for preparing these products. The reported water-soluble porphine salts are mainly sodium / potassium salts of divalent transition metal porphine chelates, such as sodium zinc chlorophyllin (sodium zinc chlorophyllin), potassium zinc chlorophyllin (potassium zinc chlorophyllin), sodium manganese chlorophyllin (sodium manganese chlorophyllin), sodium copper chlorophyllin, etc. These sodium / potassium salts have good solubility and their conventional aqueous solutions are relatively alkaline. However, there are few reports on sodium / potassium salts of trivalent transition metal porphine chelates. Hemin is a trivalent iron porphine chelate. The chlorine axially bound to the central iron is easily replaced by the hydroxyl group with stronger coordination ability. When alkali is added to the aqueous solution, hemin becomes sodium hydroxyhemoglobin (Properties and Detection Methods of Hemin, Chinese Journal of Biochemical Pharmacology, 1993.66(4):58-59). Experiments have shown that precipitation from alkaline aqueous solution can only produce sodium hydroxyhemoglobin but not sodium hemin. The use of sodium iron chlorophyllin and sodium copper chlorophyllin has shown that their products have good water solubility, significantly improved stability of solid samples, and are easy to transport and carry. However, at present, there are no reports on the research and application of natural porphin salts as plant growth regulators.
[0003] Plant immune inducers (also known as plant vaccines) are a new class of biopesticides that have emerged in recent years based on vaccine engineering technology. By regulating plant metabolism and growth, they activate the plant immune system, effectively controlling crop diseases (disease prevention), enhancing crop resistance, and simultaneously increasing yields and improving quality. They are also harmless to humans and animals and do not pollute the environment, making them a popular target in current biopesticide research and development. Currently discovered plant immune inducers primarily include small molecules derived from plants or microorganisms, such as salicylic acid and matrine, macromolecules such as humic acid and lentinan, and some chemically synthesized fungicides. Research and application of natural porphin salts as plant immune inducers (plant vaccines) have yet to be reported.
[0004] Naturally derived porphine has a planar parent ring with high electron density, which can easily chelate metal ions to form chelates such as chlorophyll heme. The outer side of the porphine ring is connected to alkyl or alkenyl groups and groups such as carboxyalkyl groups. The structure is complex and there are many isomers. For example, the acid-type dihydrochlorin iron is basically insoluble in water and has poor light and heat stability. Studies have found that the planar dihydrochlorin iron molecule has strong association / aggregation characteristics. In addition, the high lipophilicity of the molecule as a whole makes the lattice energy large, making it difficult for the solid to diffuse / disperse and dissolve (K sp As the storage time increases, the association / aggregation is further aggravated, resulting in a further decrease in solubility (K spgradually decreases); in solution, the stability of the compound also decreases significantly (A preliminary study on the basic properties of dihydrochlorin iron solution, Journal of Nanjing Normal University (Natural Science Edition), 43:1, 2020, 3:143-148). It can be seen that most acid-type porphyrin molecules have low polarity, strong fat solubility and poor water solubility. They are generally insoluble or difficult to dissolve in water, and are photothermally unstable under normal conditions. Although the product can be stored in a solid state at low temperature for a sufficient shelf life, it is easily decomposed by light in the solution, especially in aqueous solution. Strict operation is required for field use to obtain good results, which reduces the convenience of product use and increases the uncertainty of the product's use effect. For this reason, it is necessary to develop products with good stability, ease of use and strong activity to meet the needs of actual use.
[0005] Summary of the Invention
[0006] Purpose of the invention: To solve the problems existing in the prior art, the present invention provides natural porphin salts and their use as plant growth regulators and immune inducers. The natural porphin salts have good light and heat stability, strong activity, good control effect, can be quickly prepared into aqueous solutions, and are easy to use in the field.
[0007] Technical solution: In order to achieve the above purpose, the present invention adopts the following technical solution:
[0008] The present invention prepares a series of porphine salts of natural origin, including salts of porphine compounds or salts of dihydrochlorin compounds.
[0009] The porphin compounds or dihydrochlorin compounds used in the present invention are of natural origin, wherein the porphin compounds include protoporphyrin and a series of protoporphyrin chelates, and the dihydrochlorin compounds include pheophorbide and a series of pheophorbide chelates.
[0010] The salts of the porphin compounds of the present invention are prepared by forming salts of acidic protoporphyrin or its series of chelates with metal ions essential for plant nutrition; the acidic protoporphyrin and its series of chelates include protoporphyrin, hemin chloride (heme), and hydroxyheme; the metal ions essential for plant nutrition include conventional monovalent, divalent, or trivalent ions of sodium, potassium, ammonium, magnesium, calcium, iron, zinc, manganese, and copper;
[0011] Protoporphyrin is a product obtained by removing chelated iron from heme extracted from animal blood. It is a naturally derived porphin structure.
[0012] The salts of the chlorin compounds of the present invention are prepared by forming salts of acid-type pheophorbide (chlorin) and its series of chelates with metal ions essential for plant nutrition. The acid-type pheophorbide and its series of acid-type chelates include: pheophorbide (chlorin), ferric chloride (ferric chlorin), ferric hydroxychlorophyllin (ferric hydroxychlorin), ferric chlorophyllin (ferrous chlorophyllin, ferrous chlorophyllin or ferric chlorophyllin II), zinc chlorophyllin (zinc chlorophyllin), copper chlorophyllin (copper chlorophyllin); the metal ions essential for plant nutrition include: conventional monovalent, divalent or trivalent ions of sodium, potassium, ammonium, magnesium, calcium, iron, zinc, manganese and copper.
[0013] Chlorin, also known as pheophorbide, is a product obtained by hydrolyzing chlorophyll extracted from plants or silkworm feces to remove metallic magnesium. It is a mixture of various monomers with a chlorin parent core structure, mainly containing: pheophorbide a, pyropheophorbide a, chlorin e6, chlorin e4, chlorin f, chlorin p6 and purpurin 18 and other monomer compounds.
[0014] The porphine salt of the present invention can be prepared using commercially available chlorophyllin products such as pheophorbide (sodium salt), chlorophyllin copper sodium salt, chlorophyllin iron sodium salt, chlorophyllin zinc sodium salt, dihydrochlorin iron, protoporphyrin sodium or heme as raw materials, and generally a porphine salt product with a content of more than 95% (determined by photometry) can be obtained.
[0015] The preparation of the salt of the porphin compound or dihydrochlorin compound of the present invention, wherein the monovalent metal ion salt can be prepared by preparing a solution of the acidic porphin compound or dihydrochlorin compound with alcohol as a solvent, mixing it with an alcohol solution of a monovalent metal hydroxide for precipitation, or forming a salt of the acidic porphin compound or dihydrochlorin compound with an aqueous solution of a monovalent metal hydroxide and then precipitating it with acetone as a solvent, or preparing a solution of the acidic porphin compound or dihydrochlorin compound with a monovalent metal hydroxide with acetone as a solvent, then introducing dry ammonia gas for precipitation, and finally filtering, washing and drying to obtain the salt.
[0016] The monovalent metal hydroxides include sodium hydroxide, potassium hydroxide, ammonia water, and the like.
[0017] The monovalent metal ion salts of the porphyrin compounds or dihydrochlorin compounds of the present invention include: potassium protoporphyrin, ammonium protoporphyrin, sodium hemin chloride (sodium hemin, the same below), potassium hemin chloride, ammonium hemin chloride, potassium hydroxyhemin, ammonium hydroxyhemin, sodium chlorin iron salt (sodium chlorophyllin iron salt, the same below), potassium chlorin iron salt, ammonium chlorin iron salt, potassium hydroxychlorophyllin iron salt, sodium hydroxychlorophyllin iron salt, ammonium hydroxychlorophyllin iron salt, potassium chlorophyllin iron salt, ammonium chlorophyllin iron salt, sodium chlorin iron salt (sodium pheophorbide, the same below), potassium chlorin, ammonium chlorin, zinc ammonium chlorophyllin, copper ammonium chlorophyllin, and the like.
[0018] The preparation of the salts of the porphin compounds or dihydrochlorin compounds of the present invention, wherein the divalent or trivalent metal ion salt can be conveniently prepared by mixing an aqueous solution of the sodium / potassium salt of the porphin compound or dihydrochlorin compound with an aqueous solution of a soluble divalent or trivalent metal ion salt, precipitating, filtering, washing and then drying.
[0019] The above-mentioned soluble divalent or trivalent metal ion salts include sulfates, hydrochlorides, nitrates, etc. of divalent or trivalent metal ions.
[0020] The divalent metal ion salts of the porphyrin compounds or dihydrochlorin compounds of the present invention include: protoporphyrin magnesium, protoporphyrin calcium, protoporphyrin ferrous, protoporphyrin manganese, protoporphyrin zinc, protoporphyrin copper, hemin magnesium, hemin calcium, hemin ferrous, hemin manganese, hemin zinc, hemin copper, hydroxyhemoglobin magnesium, hydroxyhemoglobin calcium, hydroxyhemoglobin ferrous, hydroxyhemoglobin manganese, hydroxyhemoglobin zinc, hydroxyhemoglobin copper, dihydrochlorin iron magnesium salt, dihydrochlorin iron calcium salt, dihydrochlorin iron ferrous salt, dihydrochlorin iron manganese salt, dihydrochlorin iron zinc salt, dihydrochlorin iron copper salt, hydroxychlorophyllin iron magnesium salt, hydroxychlorophyllin iron salt, Chlorophyllin iron calcium salt, hydroxychlorophyllin iron ferrous salt, hydroxychlorophyllin iron manganese salt, hydroxychlorophyllin iron zinc salt, hydroxychlorophyllin iron copper salt, chlorophyllin iron magnesium salt, chlorophyllin iron calcium salt, chlorophyllin iron ferrous salt, chlorophyllin iron manganese salt, chlorophyllin iron zinc salt, chlorophyllin iron copper salt, dihydrochlorin magnesium salt, dihydrochlorin ferrous salt, dihydrochlorin manganese salt, dihydrochlorin zinc salt, dihydrochlorin copper salt, chlorophyllin zinc magnesium salt, chlorophyllin zinc calcium salt, chlorophyllin zinc ferrous salt, chlorophyllin zinc manganese salt, chlorophyllin zinc zinc salt, chlorophyllin zinc copper salt, chlorophyllin copper magnesium salt, chlorophyllin copper calcium salt, chlorophyllin copper ferrous salt, chlorophyllin copper manganese salt, chlorophyllin copper zinc salt, chlorophyllin copper copper salt, etc.
[0021] The trivalent metal ion salts of the porphyrin compounds or dihydrochlorin compounds of the present invention include: protoporphyrin iron salts, hemin chloride iron salts, hydroxyhemin iron salts, dihydrochlorin iron salts (chlorophyllin iron salts), hydroxychlorophyllin iron salts, chlorophyllin iron salts, dihydrochlorin iron salts, chlorophyllin zinc iron salts, chlorophyllin copper iron salts, etc.
[0022] The porphine salts of the present invention are used as plant growth regulators or plant immune inducers, and the porphine salts referred to include:
[0023] Sodium, potassium, ammonium, magnesium, calcium, ferrous, ferric, zinc, manganese and copper salts of protoporphyrin,
[0024] Sodium, potassium, ammonium, magnesium, calcium, ferrous, ferric, zinc, manganese, and copper salts of hemin,
[0025] Sodium, potassium, ammonium, magnesium, calcium, ferrous, ferric, zinc, manganese and copper salts of hydroxyhemoglobin,
[0026] Sodium, potassium, ammonium, magnesium, calcium, ferrous, ferric, zinc, manganese and copper salts of chlorin iron,
[0027] Sodium, potassium, ammonium, magnesium, calcium, ferrous, ferric, zinc, manganese and copper salts of ferric hydroxychlorophyllin,
[0028] Sodium, potassium, ammonium, magnesium, calcium, ferrous, ferric, zinc, manganese and copper salts of ferric chlorophyllin,
[0029] Sodium, potassium, ammonium, magnesium, calcium, ferrous, ferric, zinc, manganese and copper salts of chlorins,
[0030] Sodium, potassium, ammonium, magnesium, calcium, ferrous, iron, zinc, manganese and copper salts of zinc chlorophyllin,
[0031] Sodium, potassium, ammonium, magnesium, calcium, ferrous, ferric, zinc, manganese and copper salts of copper chlorophyllin.
[0032] The porphine salt of the present invention maintains the macrocyclic structure of porphine, and the Soret band and Q band of the ultraviolet and visible spectrum still have characteristic absorption, and the maximum absorption peak of each band (λ max ) Due to the influence of salt-forming metal ions, the acidic porphyrin produces a certain shift. Although the Q band absorption in the visible light region is relatively weak, the porphyrin salt products still maintain a darker color. In aqueous solution, its Soret band spectrum (360-420nm) has strong absorption and it is easy to observe the difference. Therefore, it can be used as an identification or verification of the salt-forming product (Ultraviolet-visible spectrum of porphyrin and its derivatives, Spectral Laboratory, 28:3, 2011, 5:1165-1169). It is also the basic basis for the photometric determination of the content of porphyrin products (National Food Safety Standard, Food Additive Chlorophyllin Copper Potassium Salt GB1886.307-2020). Compared with acidic porphyrin, the electron density of the conjugated structure of the porphyrin ring increases due to the electron-donating properties of the metal in porphyrin salts. The Soret band λ max There is a red shift. The stronger the metallicity, the greater the red shift. For example, hemoglobin (20% methanol aqueous solution) λ max =368nm, its alkali metal and alkaline earth metal salts (in aqueous solution): heme sodium, heme potassium, heme magnesium, heme calcium λ max The red shift is to 393nm~395nm. The transition metal salts can affect the change of porphine electron density due to factors such as d orbital participation in conjugation, ion valence, element electronegativity and d electron number. Therefore, λ max The red shift amplitude varies, such as hemoglobin manganese salt 395nm, λ max The red shift is the same as that of alkali metal salts, which may be related to the valence layer d 5 The electronic structure is related to the small electronegativity of manganese (1.5); heme zinc salt 377nm, valence layer d 10The electronegativity of zinc (1.6) is slightly greater than that of manganese, and the red shift amplitude is significantly reduced; heme iron (II) salt and heme iron (III) salt, λ max are 371nm and 373nm respectively, which corresponds to the high number of electrons provided by the high valence state of iron, while the λ max The wavelengths of the protoporphyrin ring are 362 nm and 356 nm respectively. There is no chelated metal on the protoporphyrin ring, but the iron (III) salt has a blue shift, which may be related to its valence layer d 5 The structure is easy to accept feedback electrons and reduce the conjugated electron density of porphine; the blue shift λ of hemoglobin copper salt max is 367nm, possibly related to the copper valence layer d 9 It is related to its structural characteristics and large electronegativity of 1.9.
[0033] The porphine salts of the present invention exhibit a distinct dehydration endothermic process (88-120° C.) by thermal analysis (DTA / TG). Thermogravimetric (TG) measurements show that monovalent metal salts typically dehydrate 2 moles of water and divalent metal salts dehydrate 3 moles of water. In contrast, the acidic porphine typically exhibits no significant weight loss before decomposition, or a weight loss significantly lower than that of the corresponding salts, indicating that the acidic sample contains no or very little water and has a dense solid internal structure. Differential thermal analysis (DTA) reveals that the porphine salts often exhibit distinct or prominent endothermic / exothermic peaks. After dehydration of the sample, the specific heat of the system gradually increases with increasing temperature, but there is no characteristic phase transition peak. The decomposition temperature is mostly higher than that of the corresponding acidic porphine. Due to the relatively high dehydration temperature and the large endothermic range (large energy required for dehydration), it is indicated that the small amount of solid water adsorbed by the porphine after salt formation exists mainly in the form of hydrated ions. The differential thermal curve of the acidic porphine is relatively flat, with neither endothermic nor exothermic peaks being distinct.
[0034] The porphin salts of the present invention have good water solubility, monovalent metal ion salts, and divalent / trivalent metal ion salts that are soluble or slightly soluble in water, and the solubility of both is significantly higher than that of the corresponding acid-type porphin. The porphin salt aqueous solution is neutral or even weakly acidic (pH=6.5-7.5) at the dilute concentration used in the present invention (10ppm-0.001ppm), which is suitable for plant physiological requirements, and has good light and heat stability. Accelerated tests show that the content of the porphin salt solid does not change after storage for more than two years, the aqueous solution does not significantly degrade under shading, and the content of the aqueous solution does not significantly decrease after 2-3 hours under normal lighting conditions (non-direct strong light). Therefore, the porphin salt can meet the needs of field use and is convenient to use.
[0035] Experiments have shown that the porphine salt aqueous solution of the present invention has a significantly higher content than the existing acid-type products hemin and dihydrochlorin iron when exposed to direct high-intensity light (illuminance 30,000 lux) for 1 to 3 hours.
[0036] The porphin salt of the present invention can be conveniently diluted to prepare a solution with a porphin salt content of 0.01ppm to 10ppm (about 0.014μmol / L to 14.0μmol / L) by directly adding water and stirring, and can be used as a plant growth regulator or plant immune inducer.
[0037] A 0.001ppm to 0.1ppm solution of the porphine salt of the present invention can be used for seed soaking and crop field irrigation; a 0.01ppm to 10.0ppm solution can be used for foliar spraying of crops. This promotes seed germination, increases germination rate, increases root length, promotes root growth, enhances plant immunity and stress resistance, accelerates seedling growth, increases chlorophyll content, delays premature aging of plants, and increases yield and quality.
[0038] The porphin salts of the present invention still retain the chlorophyllase inhibitory effect of acid-type dihydrochlorins. In vitro tests have shown that the chlorophyllase inhibition rate increases with the increase of salt sample concentration, indicating that it is a typical competitive inhibitor. Tests have also shown that the porphin salts of the present invention have multiple plant signal regulation effects, such as regulating the NO concentration in crop roots to promote root growth, inducing increased SOD, CAT and POD activities in plant leaves under salt stress, and promoting the release of proline in the body, thereby reducing oxidative damage caused by salt stress, enhancing crop resistance, and significantly alleviating the phytotoxicity caused by herbicides, thereby significantly increasing crop yields. In vitro tests on blight resistance have shown that the porphyrin salts of the present invention have excellent plant immune inducing activity, can significantly reduce the infection of pepper Phytophthora capsici, and have a significant preventive and therapeutic effect on blight of pepper plants artificially inoculated with Phytophthora capsici spores. The spraying of a 2.0 ppm solution has a prevention effect of 71.89%. Field tests on the spraying of a 0.2 ppm solution of sodium dihydrochlorin iron salt for the prevention and control of tobacco diseases have shown a prevention effect of 71.00%. These results can significantly improve plant stress resistance, thereby increasing crop yield.
[0039] Technical Effects: Compared to existing technologies, the porphin salts of the present invention offer excellent stability, reliable long-term storage quality, a long shelf life, and ease of transport. They are highly water-soluble, easily prepared into aqueous solutions with stable content and good reproducibility for field use. They also offer low concentrations, strong activity, high efficacy, and ease of use. The raw materials are natural and abundant, resulting in emission-free and pollution-free preparation, energy conservation, and environmental protection. In particular, as immune inducers, they offer high efficacy and significantly superior results to existing products. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1: Comparison of DTA / TG (differential thermal analysis / thermogravimetric analysis) of sodium chlorophyllin and ferric chlorophyllin: Top: DTA (differential thermal analysis); Bottom: TG (thermogravimetric analysis)
[0041] Figure 2: UV absorbance scanning spectra of the stability test of hemin and hemin magnesium solutions after strong light irradiation for 3 hours. DETAILED DESCRIPTION
[0042] The present invention will be further illustrated below with reference to specific examples.
[0043] Example 1: 5.0 g of protoporphyrin was weighed and dissolved in 1000 ml of ethanol. 12.0 ml of a 10% potassium hydroxide ethanol solution was slowly added dropwise while stirring. The mixture was placed in a refrigerator overnight, filtered, washed with cold ethanol, and dried under reduced pressure to obtain about 4.35 g of protoporphyrin potassium salt, a purple-brown solid. It decomposed at >302°C (DTA / TG), was easily soluble in water, and had a λ max =372nm (aqueous solution).
[0044] Example 2: 5.0 g of protoporphyrin was weighed and dissolved in 1000 ml of acetone. Dry ammonia was slowly introduced into the mixture under stirring until saturation. The mixture was allowed to stand overnight, filtered, washed with a small amount of cold acetone, and dried under reduced pressure to obtain about 3.11 g of protoporphyrin ammonium salt as a purple-brown solid. It decomposed at >296°C (DTA / TG), was easily soluble in water, and had a λ max =371nm (aqueous solution).
[0045] Example 3: 5.0 g of sodium protoporphyrin was weighed and dissolved in 100 ml of water with stirring. 5.0 g of magnesium sulfate was weighed and dissolved in 50 ml of water with stirring. The two solutions were slowly mixed under stirring. Stirring was continued for 1 hour and then allowed to stand overnight. The mixture was filtered, washed with cold water, and dried under reduced pressure to obtain about 3.50 g of magnesium protoporphyrin as a purple-brown solid. The solid decomposed at >361°C (DTA / TG), was soluble in water, and had a λ max =355nm (aqueous solution).
[0046] Example 4: 5.0 g of sodium protoporphyrin was weighed and dissolved in 100 ml of water with stirring. 4.5 g of calcium sulfate was weighed and dissolved in 50 ml of water with stirring. The two solutions were slowly mixed under stirring. Stirring was continued for 1 hour and then allowed to stand overnight. The mixture was filtered, washed with cold water, and dried under reduced pressure to obtain about 3.93 g of calcium protoporphyrin as a purple-brown solid. It decomposed at >365°C (DTA / TG), was soluble in water, and had a λ max =356nm (aqueous solution).
[0047] Example 5: 5.0 g of sodium protoporphyrin was weighed and dissolved in 100 ml of water with stirring. 6.0 g of manganese sulfate was weighed and dissolved in 50 ml of water with stirring. The two solutions were slowly mixed under stirring. Stirring was continued for 1 hour and then allowed to stand overnight. The mixture was filtered, washed with cold water, and dried under reduced pressure to obtain about 3.83 g of manganese protoporphyrin as a purple-brown solid. It decomposed at >367°C (DTA / TG), was soluble in water, and had a λ max =357nm (aqueous solution).
[0048] Example 6: 5.0 g of sodium protoporphyrin was weighed and dissolved in 100 ml of water with stirring. 6.5 g of ferrous sulfate was weighed and dissolved in 50 ml of water with stirring. The two solutions were slowly mixed under stirring. Stirring was continued for 1 hour and then allowed to stand overnight. The mixture was filtered, washed with cold water, and dried under reduced pressure to obtain about 4.51 g of ferrous protoporphyrin as a purple-brown solid. It decomposed at >359°C (DTA / TG), was soluble in water, and had a λ max =362nm (aqueous solution).
[0049] Example 7: 5.0 g of sodium protoporphyrin was weighed and dissolved in 100 ml of water with stirring. 4.5 g of ferric chloride was weighed and dissolved in 50 ml of water with stirring. The two solutions were slowly mixed under stirring, and stirring was continued for 1 hour. Then, the mixture was allowed to stand for 1 hour, filtered, washed with cold water, and dried under reduced pressure to obtain about 4.63 g of protoporphyrin iron salt as a purple-brown solid. It decomposed at >367°C (DTA / TG), was slightly soluble in water, and had a λ max =356nm (aqueous solution).
[0050] Example 8: 5.0 g of sodium protoporphyrin was weighed and dissolved in 100 ml of water with stirring. 5.0 g of zinc sulfate was weighed and dissolved in 50 ml of water with stirring. The two solutions were slowly mixed under stirring. Stirring was continued for 1 hour and then allowed to stand overnight. The mixture was filtered, washed with cold water, and dried under reduced pressure to obtain about 4.23 g of zinc protoporphyrin as a purple-brown solid. It decomposed at >361°C (DTA / TG), was slightly soluble in water, and had a λ max =358nm (aqueous solution).
[0051] Example 9: 5.0 g of sodium protoporphyrin was weighed and dissolved in 100 ml of water with stirring. 6.0 g of copper sulfate was weighed and dissolved in 50 ml of water with stirring. The two solutions were slowly mixed under stirring. Stirring was continued for 1 hour and then allowed to stand overnight. The mixture was filtered, washed with cold water, and dried under reduced pressure to obtain about 4.72 g of copper protoporphyrin as a purple-brown solid. The solid decomposed at >363°C (DTA / TG), was slightly soluble in water, and had a λ max =382nm (aqueous solution).
[0052] Example 10: 10.0 g of hemin was weighed and dissolved in 1000 ml of ethanol. 25.0 ml of a 10% potassium hydroxide ethanol solution was slowly added dropwise with stirring. The mixture was allowed to stand overnight, filtered, washed with cold ethanol, and dried under reduced pressure to obtain about 7.14 g of hemin potassium salt as a black solid powder. The powder decomposed at >251°C (DTA / TG), was easily soluble in water, and had a λ max =394nm (aqueous solution).
[0053] Example 11: 10.0 g of hemin was weighed and dissolved in 1000 ml of ethanol. 25.0 ml of a 10% sodium hydroxide ethanol solution was slowly added dropwise with stirring. The mixture was allowed to stand overnight, filtered, washed with cold ethanol, and dried under reduced pressure to obtain about 9.33 g of hemin sodium salt as a black solid powder. The powder decomposed at >264°C (DTA / TG), was easily soluble in water, and had a λ max =393nm (aqueous solution).
[0054] Comparative sample: Preparation of hydroxyhemoglobin sodium salt
[0055] According to the literature (Preparation of sodium hemin, Chemical World, 2004.10: 540-541): 10.0 g of hemin was dissolved in 120 ml of 0.2 mol / L NaOH solution, stirred for 6 hours, filtered, and 1000 ml of acetone (more than 8 times the amount) was slowly added to the filtrate to precipitate a black precipitate. The precipitate was allowed to stand overnight, filtered, washed with a little acetone, and dried under reduced pressure to obtain 8.7 g of a black solid, which was easily soluble in water and had a λ max =384nm (aqueous solution).
[0056] Comparative experiment 1: Cl - Ion detection
[0057] Reagents: HNO3 solution (4 mol / L), AgNO3 test solution (0.1 mol / L)
[0058] Method: Take the filtrate (reaction mother liquor) after preparing the precipitation and filtration product as mentioned above, respectively, and recover the solvent ethanol or acetone by rotary evaporation until complete, cool to obtain the residual solid, add about 20 ml of pure water to dissolve each, and then adjust to neutrality (pH≈7) with HNO3 to obtain the test solution; take a small amount of the test solution (0.5-1 ml) and add it to a test tube, add a few drops of AgNO3 test solution, observe whether there is precipitation / turbidity, and if turbidity occurs, continue to slowly add a small amount of HNO3 and observe the changes.
[0059] Result: The test solution obtained after the ethanol filtrate was recovered was not turbid and no Cl was detected. - ion.
[0060] After the acetone filtrate was recovered, the solution to be tested produced a precipitate (AgCl↓). After adding HNO3, the precipitate did not change. Cl was detected. - ion.
[0061] Note: The product prepared in ethanol (this example) is sodium hemin. During the preparation of a comparative sample using acetone precipitation from an alkaline hemin solution (as described in the literature), chloride ions were replaced by hydroxyl groups and entered the reaction solution (forming NaCl). The resulting product is chloride-free (replaced by hydroxyl groups) and should be sodium hydroxyhemin, not sodium hemin.
[0062] Comparative test 2: Sample UV maximum absorption wavelength (λ max ) determination
[0063] Samples: sodium hemin, sodium hydroxyhemin, hemin chloride
[0064] Reagents: pure water, 0.1 mol / L NaOH solution
[0065] Instrument: Shimadzu UV2600 UV spectrophotometer
[0066] Method: Weigh an appropriate amount of sample, dissolve it with pure water or NaOH solution, and then dilute it to a solution with a concentration of about 20.0ppm. Scan the sample with a UV spectrometer to determine the maximum absorption wavelength λ max (Structural characteristics), the results are shown in the following table:
[0067] The maximum UV absorption wavelength (λ max )
[0068]
[0069] Results: In NaOH solution, the characteristic absorption of the three samples is 384nm, which indicates that the axial chlorine group bound to the central iron in hemin is at a higher OH - At low ion concentrations, it is replaced by hydroxyl groups to generate the product sodium hydroxyhemoglobin. In the solution prepared with aqueous solution, OH - The ion concentration is not high (pH = 7.5 of 20 ppm sodium hemin solution), and the chlorine group is retained. The sample of this embodiment shows a characteristic absorption of sodium hemin at 393 nm. The characteristic value of the comparative sample prepared by the literature method is exactly the same as that of the NaOH solution, indicating that the sample is sodium hydroxyhemin.
[0070] The chlorine and hydroxyl groups axially coordinating the iron core of the heme have different electron-donating and electron-withdrawing abilities, and the resulting interaction is related to the element's electronegativity, lone electron pairs, and valence shell electron structure. Chlorine has an electronegativity of 3.0 and a 3p valence shell structure, making five lone electron pairs available when axially bound to the iron core. The oxygen in the hydroxyl group has an electronegativity of 3.5 and a 2p valence shell structure, making four lone electron pairs available when axially bound to the iron core. This suggests that, compared to chlorine, the hydroxyl group has stronger electron-withdrawing and weaker electron-donating abilities. Consequently, hydroxyl coordination reduces the electron density of the porphine conjugated structure, resulting in a blue shift of the characteristic Soret absorption band from 393 nm to 384 nm in sodium hydroxyheme.
[0071] Example 12: 5.0 g of hemin was weighed and dissolved in 1000 ml of acetone. Dry ammonia was slowly introduced into the mixture under stirring until saturation. The mixture was allowed to stand overnight, filtered, washed with a little cold acetone, and dried under reduced pressure to obtain about 3.60 g of hemin ammonium salt as a brown solid. It decomposed at >243°C (DTA / TG), was easily soluble in water, and had a λmax =386nm (aqueous solution).
[0072] Example 13: Weigh 10.0 g of hemin sodium salt and stir and dissolve it in 200 ml of water. Separately, weigh 11.0 g of magnesium sulfate and stir and dissolve it in 100 ml of water. Slowly mix the two solutions while stirring, continue stirring for 1 hour, then let stand overnight, filter, wash with cold water, and dry under reduced pressure to obtain about 7.19 g of hemin magnesium salt as a dark brown solid. Decompose at >292°C (DTA / TG), soluble in water, λ max =395nm (aqueous solution).
[0073] Example 14: Weigh 10.0 g of sodium hemin salt and stir and dissolve it in 200 ml of water. Separately, weigh 9.0 g of calcium chloride and stir and dissolve it in 100 ml of water. Slowly mix the two solutions while stirring, continue stirring for 1 hour, let stand overnight, filter, wash with cold water, and dry under reduced pressure to obtain about 7.37 g of calcium hemin salt as a dark brown solid. Decompose at >311°C (DTA / TG), soluble in water, λ max =395nm (aqueous solution).
[0074] Example 15: Weigh 10.0 g of hemin sodium salt and stir and dissolve it in 200 ml of water. Separately, weigh 11.0 g of manganese sulfate and stir and dissolve it in 150 ml of water. Slowly mix the two solutions while stirring. Continue stirring for 1 hour and then let it stand overnight. Filter, wash with cold water, and dry under reduced pressure to obtain about 8.57 g of hemin manganese salt as a dark brown solid. Decompose at >329°C (DTA / TG), slightly soluble in water, λ max =395nm (aqueous solution).
[0075] Example 16: Weigh 10.0 g of sodium hemin salt and stir and dissolve it in 200 ml of water. Separately, weigh 14.0 g of ferrous sulfate and stir and dissolve it in 150 ml of water. Slowly mix the two solutions while stirring. Continue stirring for 1 hour and then let it stand overnight. Filter, wash with cold water, and dry under reduced pressure to obtain about 8.63 g of ferrous hemin salt as a dark brown solid. Decompose at >327°C (DTA / TG), slightly soluble in water, λ max =373nm (aqueous solution).
[0076] Example 17: Weigh 10.0 g of sodium hemin salt and stir and dissolve it in 200 ml of water. Separately, weigh 11.0 g of ferric chloride and stir and dissolve it in 120 ml of water. Slowly mix the two solutions while stirring, continue stirring for 1 hour, then let it stand overnight, filter, wash with cold water, and dry under reduced pressure to obtain about 9.06 g of ferric hemin salt as a dark brown solid. It decomposes at >334°C (DTA / TG), is slightly soluble in water, and has a λ max =371nm (aqueous solution).
[0077] Example 18: Weigh 10.0 g of hemin sodium salt and stir and dissolve it in 200 ml of water. Separately, weigh 14.0 g of zinc sulfate and stir and dissolve it in 150 ml of water. Slowly mix the two solutions while stirring. Continue stirring for 1 hour and then let it stand overnight. Filter, wash with cold water, and dry under reduced pressure to obtain about 9.13 g of hemin zinc salt as a dark brown solid. Decompose at >274°C (DTA / TG), slightly soluble in water, λ max =377nm (aqueous solution).
[0078] Example 19: Weigh 10.0 g of sodium hemin salt and stir and dissolve it in 200 ml of water. Separately, weigh 15.0 g of copper sulfate and stir and dissolve it in 150 ml of water. Slowly mix the two solutions while stirring. Continue stirring for 1 hour and then let it stand overnight. Filter, wash with cold water, and dry under reduced pressure to obtain about 9.06 g of copper hemin salt as a dark brown solid. Decompose at >248°C (DTA / TG), slightly soluble in water, λ max =367nm (aqueous solution).
[0079] Example 20: 1000.0 g of chlorin iron parent drug (produced by Nanjing Baxter Bioengineering Co., Ltd., the same below) was weighed and mixed with 15 liters of industrial alcohol. The mixture was stirred until fully dissolved. 2.5 liters of 15% potassium hydroxide ethanol solution was slowly added dropwise. The precipitate was allowed to stand overnight, filtered, washed with cold ethanol, and dried under reduced pressure to obtain 896.0 g of chlorin iron potassium salt as a dark green powder. It decomposed at >313°C (DTA / TG), was easily soluble in water, and had a λ max =400nm (aqueous solution).
[0080] Example 21: 1000.0 g of chlorin iron parent drug was weighed and mixed with 15 liters of industrial alcohol to fully dissolve. 2.3 liters of 15% sodium hydroxide ethanol solution was slowly added dropwise. The precipitate was allowed to stand overnight, filtered, washed with cold ethanol, and dried under reduced pressure to obtain 907 g of chlorin iron sodium salt as a dark green powder. It decomposed at >301°C (DTA / TG), was easily soluble in water, and had a λ max =399nm (aqueous solution).
[0081] Example 22: 100.0 g of chlorin iron parent drug was weighed and mixed with 1.5 L of acetone to dissolve it. Dry ammonia was slowly introduced to produce a precipitate. The precipitate was allowed to stand overnight, filtered, washed with cold acetone, and dried under reduced pressure to obtain about 51.2 g of chlorin iron ammonium salt as a dark green powder. It decomposed at >270°C (DTA / TG), was easily soluble in water, and had a λ max =401nm (aqueous solution).
[0082] Example 23: Weigh 100.0 g of sodium chlorin iron salt and stir and dissolve it in 1 liter of water. Separately, weigh 110.0 g of magnesium chloride hexahydrate and stir and dissolve it in 500 ml of water. Slowly mix the two solutions at room temperature with stirring to produce a precipitate. The precipitate is stored in the dark overnight, filtered, washed twice with cold water, filtered, and dried under reduced pressure to obtain 73.1 g of magnesium chlorin iron salt as a dark green powder. It decomposes at >302°C (DTA / TG), is soluble in water, and has a λ max =400nm (aqueous solution).
[0083] Example 24: Weigh 100.0 g of sodium chlorin iron salt and stir and dissolve it in 1 liter of water. Separately, weigh 100.0 g of calcium chloride dihydrate and stir and dissolve it in 500 ml of water. Slowly mix the two solutions at room temperature with stirring to produce a precipitate. The precipitate is stored in the dark overnight, filtered, washed with cold water, filtered, and dried under reduced pressure to obtain 80.2 g of calcium chlorin iron salt as a dark green powder. It decomposes at >377°C (DTA / TG), is soluble in water, and has a λ max =399nm (aqueous solution).
[0084] Example 25: Weigh 100.0 g of sodium chlorin iron salt and stir and dissolve it in 1 liter of water. Separately, weigh 110.0 g of ferrous chloride tetrahydrate and stir and dissolve it in 500 ml of water. Slowly mix the two solutions at room temperature with stirring to produce a precipitate. The precipitate is stored in the dark overnight, filtered, washed with cold water, filtered, and dried under reduced pressure to obtain 91.1 g of ferrous chlorin iron salt as a dark green powder. It decomposes at >303°C (DTA / TG), is slightly soluble in water, and has a λ max =401nm (aqueous solution).
[0085] Example 26: Weigh 100.0 g of sodium chlorin iron salt and stir and dissolve it in 1 liter of water. Separately, weigh 110.0 g of ferric chloride hexahydrate and stir and dissolve it in 500 ml of water. Slowly mix the two solutions at room temperature with stirring to produce a precipitate. The precipitate is stored in the dark overnight, filtered, washed with cold water, filtered, and then dried under reduced pressure to obtain 89.2 g of sodium chlorin iron salt as a dark green powder. It decomposes at >329°C (DTA / TG), is slightly soluble in water, and has a λ max =405nm (aqueous solution).
[0086] Example 27: 100.0 g of sodium chlorin iron salt was weighed and dissolved in 1 liter of water with stirring. Separately, 100.0 g of manganese chloride tetrahydrate was weighed and dissolved in 500 ml of water with stirring. The two solutions were slowly mixed under stirring at room temperature to produce a precipitate. The precipitate was stored in the dark overnight, filtered, washed with cold water, filtered, and dried under reduced pressure to obtain 87.8 g of chlorin iron manganese salt as a dark green powder. It decomposed at >299°C (DTA / TG), was slightly soluble in water, and had a λ max =400nm (aqueous solution).
[0087] Example 28: Weigh 100.0 g of sodium chlorin iron salt and stir and dissolve it in 1 liter of water. Separately, weigh 100.0 g of zinc chloride and stir and dissolve it in 500 ml of water. Slowly mix the two solutions at room temperature with stirring to produce a precipitate. The precipitate is stored in the dark overnight, filtered, washed with cold water, filtered, and dried under reduced pressure to obtain 91.4 g of sodium chlorin iron zinc salt as a dark green powder. It decomposes at >300°C (DTA / TG), is slightly soluble in water, and has a λ max =399nm (aqueous solution).
[0088] Example 29: 100.0 g of sodium chlorin iron salt was weighed and dissolved in 1 liter of water with stirring. 95.0 g of copper chloride dihydrate was weighed and dissolved in 500 ml of water with stirring. The two solutions were slowly mixed with stirring at room temperature to produce a precipitate. The precipitate was stored in the dark overnight, filtered, washed with cold water, filtered, and dried under reduced pressure to obtain 87.2 g of chlorin iron copper salt as a dark green powder. It decomposed at >222°C (DTA / TG), was slightly soluble in water, and had a λ max =398nm (aqueous solution).
[0089] Example 30: 1000.0 g of commercially available sodium chlorophyllin iron salt was weighed and dissolved in 10 liters of water with stirring. 15% dilute sulfuric acid was slowly added dropwise while stirring at room temperature until the pH was 3-4. The mixture was kept in the dark overnight, filtered, washed twice with cold water, filtered, and dried under reduced pressure. The obtained ferric chlorophyllin was mixed with 15 liters of industrial alcohol, stirred and dissolved, and 2.5 liters of 15% potassium hydroxide ethanol solution was slowly added dropwise. The precipitate was allowed to stand overnight, filtered, washed with cold ethanol, and dried under reduced pressure to obtain about 783.0 g of potassium chlorophyllin iron salt, a dark green powder that decomposed at >309°C (DTA / TG), was easily soluble in water, and had a λ max =397nm (aqueous solution).
[0090] Example 31: 100.0 g of commercially available sodium chlorophyllin iron salt was weighed and dissolved in 1 liter of water with stirring. 15% dilute sulfuric acid was slowly added dropwise with stirring at room temperature until the pH was 3-4. The mixture was kept in the dark overnight, filtered, washed twice with cold water, filtered, and then dried under reduced pressure. The obtained chlorophyllin iron salt was mixed with 1.5 liters of acetone to dissolve it. Dry ammonia gas was slowly introduced with stirring to produce a precipitate. The mixture was kept overnight, filtered, washed with cold acetone, and dried under reduced pressure to obtain about 37.2 g of chlorophyllin iron ammonium salt, a dark green powder. It decomposed at >224°C (DTA / TG), was easily soluble in water, and had a λ max =398nm (aqueous solution).
[0091] Example 32: Weigh 100.0 g of commercially available sodium ferric chlorophyllin and stir and dissolve it in 1 liter of water. Separately, weigh 120.0 g of ferrous sulfate and stir and dissolve it in 500 ml of water. Slowly mix the two solutions at room temperature with stirring to produce a precipitate. The precipitate is stored in the dark overnight, filtered, washed with cold water, filtered, and then dried under reduced pressure to obtain 90.9 g of ferrous chlorophyllin as a dark green powder. It decomposes at >278°C (DTA / TG), is slightly soluble in water, and has a λmax =400nm (aqueous solution).
[0092] Example 33: Weigh 100.0 g of commercially available sodium ferric chlorophyllin and dissolve it in 1 liter of water with stirring. Separately, weigh 90.0 g of ferric chloride and dissolve it in 500 ml of water with stirring. Slowly mix the two solutions at room temperature with stirring to produce a precipitate. The precipitate is stored in the dark overnight, filtered, washed with cold water, filtered, and dried under reduced pressure to obtain 91.6 g of ferric chlorophyllin as a dark green powder. It decomposes at >343°C (DTA / TG), is slightly soluble in water, and has a λ max =399nm (aqueous solution).
[0093] Example 34: 100.0 g of commercially available sodium ferric chlorophyllin was weighed and dissolved in 1 liter of water with stirring. Separately, 110.0 g of copper sulfate was weighed and dissolved in 500 ml of water with stirring. The two solutions were slowly mixed with stirring at room temperature to produce a precipitate. The precipitate was stored in the dark overnight, filtered, washed with cold water, filtered, and dried under reduced pressure to obtain 91.2 g of copper ferric chlorophyllin as a dark green powder. It decomposed at >208°C (DTA / TG), was slightly soluble in water, and had a λ max =401nm (aqueous solution).
[0094] Example 35: Weigh 500.0 g of commercially available sodium zinc chlorophyllin and dissolve it in 5 liters of purified water. Adjust the pH to 4-5 with dilute sulfuric acid under stirring to precipitate the precipitate, filter, wash with water, and dry to obtain zinc chlorophyllin. Weigh 100.0 g of zinc chlorophyllin and mix with 1.5 liters of acetone to dissolve it. Slowly introduce dry ammonia gas to produce a precipitate. Let it sit overnight, filter, wash with cold acetone, and dry under reduced pressure to obtain approximately 40.2 g of zinc chlorophyllin ammonium salt, a black powder that decomposes at >251°C (DTA / TG), is easily soluble in water, and has a λ max =404nm (aqueous solution).
[0095] Example 36: Weigh 100.0 g of commercially available sodium zinc chlorophyllin and dissolve it in 1 liter of water with stirring. Separately, weigh 100.0 g of magnesium chloride hexahydrate and dissolve it in 500 ml of water with stirring. Slowly mix the two solutions at room temperature with stirring to produce a precipitate. The precipitate is stored in the dark overnight, filtered, washed twice with cold water, filtered, and dried under reduced pressure to obtain 87.6 g of commercially available magnesium zinc chlorophyllin as a black powder. It decomposes at >333°C (DTA / TG), is soluble in water, and has a λ max =405nm (aqueous solution).
[0096] Example 37: Weigh 100.0 g of commercially available sodium zinc chlorophyllin and dissolve it in 1 liter of water with stirring. Separately, weigh 100.0 g of calcium chloride dihydrate and dissolve it in 500 ml of water with stirring. Slowly mix the two solutions at room temperature with stirring to produce a precipitate. The precipitate is stored in the dark overnight, filtered, washed with cold water, filtered, and dried under reduced pressure to obtain 83.7 g of calcium zinc chlorophyllin as a black powder. It decomposes at >365°C (DTA / TG), is soluble in water, and has a λ max=405nm (aqueous solution).
[0097] Example 38: 100.0 g of commercially available sodium zinc chlorophyllin was weighed and dissolved in 1 liter of water with stirring. Separately, 120.0 g of ferrous chloride tetrahydrate was weighed and dissolved in 500 ml of water with stirring. The two solutions were slowly mixed with stirring at room temperature to produce a precipitate. The precipitate was stored in the dark overnight, filtered, washed with cold water, filtered, and dried under reduced pressure to obtain 90.2 g of ferrous zinc chlorophyllin as a black powder. It decomposed at >371°C (DTA / TG), was slightly soluble in water, and had a λ max =406nm (aqueous solution).
[0098] Example 39: 100.0 g of commercially available sodium zinc chlorophyllin was weighed and dissolved in 1 liter of water with stirring. Separately, 100.0 g of ferric chloride hexahydrate was weighed and dissolved in 500 ml of water with stirring. The two solutions were slowly mixed with stirring at room temperature to produce a precipitate. The precipitate was stored in the dark overnight, filtered, washed with cold water, filtered, and dried under reduced pressure to obtain 89.8 g of ferric zinc chlorophyllin as a black powder. It decomposed at >341°C (DTA / TG), was slightly soluble in water, and had a λ max =403nm (aqueous solution).
[0099] Example 40: Weigh 100.0 g of commercially available sodium zinc chlorophyllin and dissolve it in 1 liter of water with stirring. Separately, weigh 100.0 g of manganese chloride tetrahydrate and dissolve it in 500 ml of water with stirring. Slowly mix the two solutions at room temperature with stirring to produce a precipitate. The precipitate is stored in the dark overnight, filtered, washed with cold water, filtered, and dried under reduced pressure to obtain 90.7 g of zinc manganese chlorophyllin as a black powder. It decomposes at >336°C (DTA / TG), is slightly soluble in water, and has a λ max =404nm (aqueous solution).
[0100] Example 41: Weigh 100.0 g of commercially available sodium zinc chlorophyllin and dissolve it in 1 liter of water with stirring. Separately, weigh 100.0 g of zinc chloride and dissolve it in 500 ml of water with stirring. Slowly mix the two solutions at room temperature with stirring to produce a precipitate. The precipitate is stored in the dark overnight, filtered, washed with cold water, filtered, and dried under reduced pressure to obtain 92.5 g of zinc chlorophyllin as a black powder. It decomposes at >320°C (DTA / TG), is slightly soluble in water, and has a λ max =409nm (aqueous solution).
[0101] Example 42: 100.0 g of commercially available sodium zinc chlorophyllin was weighed and dissolved in 1 liter of water with stirring. Separately, 95.0 g of copper chloride dihydrate was weighed and dissolved in 500 ml of water with stirring. The two solutions were slowly mixed with stirring at room temperature to produce a precipitate. The precipitate was stored in the dark overnight, filtered, washed with cold water, filtered, and dried under reduced pressure to obtain 90.3 g of zinc copper chlorophyllin as a black powder. It decomposed at >271°C (DTA / TG), was slightly soluble in water, and had a λ max =409nm (aqueous solution).
[0102] Example 43: 100.0 g of commercially available sodium copper chlorophyllin was weighed and dissolved in 2 liters of water with stirring. 15% dilute sulfuric acid was slowly added dropwise with stirring at room temperature until the pH was between 3 and 5. The mixture was kept in the dark overnight, filtered, washed twice with cold water, filtered, and dried under reduced pressure to obtain copper chlorophyllin. The mixture was mixed with 2 liters of industrial alcohol, stirred and dissolved, and 250 ml of 15% potassium hydroxide ethanol solution was slowly added dropwise. The precipitate was allowed to stand overnight, filtered, washed with cold ethanol, and dried under reduced pressure to obtain about 79.8 g of potassium copper chlorophyllin, a dark green powder. It decomposed at >296°C (DTA / TG), was easily soluble in water, and had a λ max =405nm (aqueous solution).
[0103] Example 44: 100.0 g of commercially available sodium copper chlorophyllin was weighed and dissolved in 2 liters of water with stirring. 15% dilute sulfuric acid was slowly added dropwise with stirring at room temperature until the pH was 3-5. The mixture was kept in the dark overnight, filtered, washed twice with cold water, filtered, and dried under reduced pressure to obtain copper chlorophyllin. The mixture was mixed with 2 liters of acetone, stirred and dissolved, and dry ammonia was slowly introduced to produce a precipitate until saturation. The precipitate was kept overnight, filtered, washed with cold acetone, and dried under reduced pressure to obtain about 44.6 g of ammonium copper chlorophyllin as a dark green powder. It decomposed at >277°C (DTA / TG), was easily soluble in water, and had a λ max =404nm (aqueous solution).
[0104] Example 45: 100.0 g of commercially available sodium copper chlorophyllin was weighed and dissolved in 1 liter of water with stirring. Separately, 100.0 g of magnesium sulfate was weighed and dissolved in 500 ml of water with stirring. The two solutions were slowly mixed with stirring at room temperature to produce a precipitate. The precipitate was stored in the dark overnight, filtered, washed with cold water, filtered, and dried under reduced pressure to obtain 74.1 g of magnesium copper chlorophyllin as a dark green powder. It decomposed at >280°C (DTA / TG), was soluble in water, and had a λ max =406nm (aqueous solution).
[0105] Example 46: Weigh 100.0 g of commercially available sodium copper chlorophyllin and dissolve it in 1 liter of water with stirring. Separately, weigh 90.0 g of calcium chloride and dissolve it in 500 ml of water with stirring. Slowly mix the two solutions at room temperature with stirring to produce a precipitate. The precipitate is stored in the dark overnight, filtered, washed with cold water, filtered, and dried under reduced pressure to obtain 87.4 g of calcium copper chlorophyllin as a dark green powder. It decomposes at >305°C (DTA / TG), is soluble in water, and has a λ max =405nm (aqueous solution).
[0106] Example 47: 100.0 g of commercially available sodium copper chlorophyllin was weighed and dissolved in 1 liter of water with stirring. Separately, 90.0 g of manganese chloride tetrahydrate was weighed and dissolved in 500 ml of water with stirring. The two solutions were slowly mixed with stirring at room temperature to produce a precipitate. The precipitate was stored in the dark overnight, filtered, washed with cold water, filtered, and dried under reduced pressure to obtain 70.3 g of copper manganese chlorophyllin as a dark green powder. It decomposed at >311°C (DTA / TG), was soluble in water, and had a λ max=405nm (aqueous solution).
[0107] Example 48: 100.0 g of commercially available sodium copper chlorophyllin was weighed and dissolved in 1 liter of water with stirring. Separately, 120.0 g of ferrous sulfate was weighed and dissolved in 500 ml of water with stirring. The two solutions were slowly mixed with stirring at room temperature to produce a precipitate. The precipitate was stored in the dark overnight, filtered, washed with cold water, filtered, and dried under reduced pressure to obtain 90.4 g of ferrous copper chlorophyllin as a dark green powder. It decomposed at >266°C (DTA / TG), was slightly soluble in water, and had a λ max =403nm (aqueous solution).
[0108] Example 49: 100.0 g of commercially available sodium copper chlorophyllin was weighed and dissolved in 1 liter of water with stirring. Separately, 90.0 g of ferric chloride was weighed and dissolved in 500 ml of water with stirring. The two solutions were slowly mixed with stirring at room temperature to produce a precipitate. The precipitate was stored in the dark overnight, filtered, washed with cold water, filtered, and dried under reduced pressure to obtain 89.7 g of copper iron chlorophyllin as a dark green powder. It decomposed at >357°C (DTA / TG), was slightly soluble in water, and had a λ max =406nm (aqueous solution).
[0109] Example 50: Weigh 100.0 g of commercially available sodium copper chlorophyllin and dissolve it in 1 liter of water with stirring. Separately, weigh 100.0 g of zinc chloride and dissolve it in 500 ml of water with stirring. Slowly mix the two solutions at room temperature with stirring to produce a precipitate. The precipitate is stored in the dark overnight, filtered, washed with cold water, filtered, and dried under reduced pressure to obtain 90.5 g of copper zinc chlorophyllin as a dark green powder. It decomposes at >263°C (DTA / TG), is slightly soluble in water, and has a λ max =404nm (aqueous solution).
[0110] Example 51: Weigh 100.0 g of commercially available sodium copper chlorophyllin and dissolve it in 1 liter of water with stirring. Separately, weigh 110.0 g of copper sulfate and dissolve it in 500 ml of water with stirring. Slowly mix the two solutions at room temperature with stirring to produce a precipitate. The precipitate is stored in the dark overnight, filtered, washed with cold water, filtered, and dried under reduced pressure to obtain 91.7 g of copper chlorophyllin as a dark green powder. It decomposes at >242°C (DTA / TG), is slightly soluble in water, and has a λ max =404nm (aqueous solution).
[0111] Example 52: Weigh 1000 g of commercially available sodium magnesium chlorophyllin, dissolve it in 20 liters of purified water preheated to 60°C, stop heating, slowly add dilute sulfuric acid dropwise until the pH is 3-4, keep it in the dark overnight, filter, wash it twice with cold water, filter press it, and then dry it under reduced pressure to obtain 886.3 g of pheophorbide (dihydrochlorin). Dissolve 100.0 g of dried dihydrochlorin in 1.6 liters of industrial alcohol, stir until fully dissolved, slowly add 300 ml of 15% potassium hydroxide ethanol solution dropwise to produce a precipitate, keep it in the dark overnight, filter, wash it with cold ethanol, and dry it under reduced pressure to obtain 69.2 g of dihydrochlorin potassium salt, a black powder that decomposes at >283°C (DTA / TG), is easily soluble in water, and has a λ max =405nm (aqueous solution).
[0112] Example 53: Weigh 1000 g of dried chlorin (prepared according to the method of Example 52), mix it with 15 liters of industrial alcohol and dissolve it completely. Slowly add 2.3 liters of 15% sodium hydroxide ethanol solution, let the precipitate stand overnight, filter, wash with cold ethanol, and dry under reduced pressure to obtain 723.0 g of chlorin sodium salt as a black powder. Decompose at >277°C (DTA / TG), soluble in water, λ max =404nm (aqueous solution).
[0113] Example 54: 100.0 g of dry chlorin (prepared according to the method of Example 52) was weighed and mixed with 1.5 L of acetone to dissolve it. Dry ammonia was slowly introduced to produce a precipitate. The precipitate was allowed to stand overnight, filtered, washed with cold acetone, and dried under reduced pressure to obtain about 37.6 g of chlorin ammonium salt as a brown powder. It decomposed at >281°C (DTA / TG), was easily soluble in water, and had a λ max =403nm (aqueous solution).
[0114] Example 55: 100.0 g of chlorin sodium salt (prepared according to the method of Example 53) was weighed and dissolved in 1 liter of water with stirring. Separately, 110.0 g of magnesium chloride hexahydrate was weighed and dissolved in 500 ml of water with stirring. The two solutions were slowly mixed with stirring at room temperature to produce a precipitate. The precipitate was stored in the dark overnight, filtered, washed twice with cold water, filtered, and dried under reduced pressure to obtain 80.7 g of chlorin magnesium salt as a dark brown powder. It decomposed at >312°C (DTA / TG), was soluble in water, and had a λ max =404nm (aqueous solution).
[0115] Example 56: 100.0 g of sodium chlorin (prepared according to the method of Example 53) was weighed and dissolved in 1 liter of water with stirring. Separately, 100.0 g of calcium chloride dihydrate was weighed and dissolved in 500 ml of water with stirring. The two solutions were slowly mixed with stirring at room temperature to produce a precipitate. The precipitate was stored in the dark overnight, filtered, washed with cold water, filtered, and dried under reduced pressure to obtain 83.1 g of calcium chlorin as a black powder. It decomposed at >373°C (DTA / TG), was soluble in water, and had a λmax =404nm (aqueous solution).
[0116] Example 57: 100.0 g of sodium chlorin (prepared according to the method of Example 53) was weighed and dissolved in 1 liter of water with stirring. Separately, 110.0 g of ferrous chloride tetrahydrate was weighed and dissolved in 500 ml of water with stirring. The two solutions were slowly mixed with stirring at room temperature to produce a precipitate. The precipitate was stored in the dark overnight, filtered, washed with cold water, filtered, and dried under reduced pressure to obtain 83.9 g of ferrous chlorin as a black powder. It decomposed at >292°C (DTA / TG), was slightly soluble in water, and had a λ max =405nm (aqueous solution).
[0117] Example 58: 100.0 g of sodium chlorin (prepared according to the method of Example 53) was weighed and dissolved in 1 liter of water with stirring. Separately, 110.0 g of ferric chloride hexahydrate was weighed and dissolved in 500 ml of water with stirring. The two solutions were slowly mixed with stirring at room temperature to produce a precipitate. The precipitate was stored in the dark overnight, filtered, washed with cold water, filtered, and dried under reduced pressure to obtain 84.5 g of ferric chlorin as a black powder. It decomposed at >303°C (DTA / TG), was slightly soluble in water, and had a λ max =403nm (aqueous solution).
[0118] Example 59: 100.0 g of chlorin sodium salt (prepared according to the method of Example 53) was weighed and dissolved in 1 liter of water with stirring. Separately, 100.0 g of manganese chloride tetrahydrate was weighed and dissolved in 500 ml of water with stirring. The two solutions were slowly mixed with stirring at room temperature to produce a precipitate. The precipitate was stored in the dark overnight, filtered, washed with cold water, filtered, and dried under reduced pressure to obtain 81.4 g of chlorin manganese salt as a black powder. It decomposed at >284°C (DTA / TG), was slightly soluble in water, and had a λ max =404nm (aqueous solution).
[0119] Example 60: 100.0 g of chlorin sodium salt (prepared according to the method of Example 53) was weighed and dissolved in 1 liter of water with stirring. Separately, 100.0 g of zinc chloride was weighed and dissolved in 500 ml of water with stirring. The two solutions were slowly mixed with stirring at room temperature to produce a precipitate. The precipitate was stored in the dark overnight, filtered, washed with cold water, filtered, and dried under reduced pressure to obtain 86.0 g of chlorin zinc salt as a black powder. It decomposed at >349°C (DTA / TG), was slightly soluble in water, and had a λ max =409nm (aqueous solution).
[0120] Example 61: 100.0 g of sodium chlorin (prepared according to the method of Example 53) was weighed and dissolved in 1 liter of water with stirring. 95.0 g of copper chloride dihydrate was weighed and dissolved in 500 ml of water with stirring. The two solutions were slowly mixed with stirring at room temperature to produce a precipitate. The precipitate was stored in the dark overnight, filtered, washed with cold water, filtered, and dried under reduced pressure to obtain 84.6 g of copper chlorin as a black powder. It decomposed at >245°C (DTA / TG), was slightly soluble in water, and had a λ max =405nm (aqueous solution).
[0121] Example 62: 10.0 g of hemin was weighed and dissolved in 1000 ml of 6.0% potassium hydroxide aqueous solution, stirred in dark for 5 hours, 8000 ml of acetone was slowly added, stirred in dark for 1 hour, and then allowed to stand overnight. The mixture was filtered, washed with cold acetone, and dried under reduced pressure to obtain about 8.37 g of hydroxyhemoglobin potassium salt as a black solid powder. The powder decomposed at >303°C (DTA / TG), was easily soluble in water, and had a λ max =388nm (aqueous solution).
[0122] Example 63: 5.0 g of potassium hydroxyhemoglobin was weighed and dissolved in 1000 ml of water. 5% sulfuric acid was slowly added dropwise with stirring in the dark until the pH was ≈ 4. The mixture was allowed to stand overnight, filtered, and the filter cake was washed with water until neutral. The solid was then dried under reduced pressure. The solid was dissolved in 1000 ml of acetone. Dry ammonia was slowly introduced into the mixture with stirring until saturation. The mixture was allowed to stand overnight, filtered, washed with a small amount of cold acetone, and dried under reduced pressure to obtain about 3.17 g of ammonium salt of hydroxyhemoglobin. The brown solid decomposed at >287°C (DTA / TG), was easily soluble in water, and had a λ max =383nm (aqueous solution).
[0123] Example 64: Weigh 10.0 g of potassium salt of hemoglobin and stir and dissolve it in 200 ml of water. Separately, weigh 12.0 g of magnesium sulfate and stir and dissolve it in 100 ml of water. Slowly mix the two solutions while stirring, continue stirring for 1 hour, then let stand overnight, filter, wash with a little cold water, and dry under reduced pressure to obtain about 7.25 g of magnesium salt of hemoglobin as a dark brown solid. Decompose at >293°C (DTA / TG), soluble in water, λ max =387nm (aqueous solution).
[0124] Example 65: Weigh 10.0 g of potassium salt of hydroxyhemoglobin and stir and dissolve it in 200 ml of water. Separately, weigh 10.0 g of calcium chloride and stir and dissolve it in 100 ml of water. Slowly mix the two solutions while stirring. Continue stirring for 1 hour and then let stand overnight. Filter, wash with cold water, and dry under reduced pressure to obtain about 7.46 g of calcium salt of hydroxyhemoglobin as a dark brown solid. Decompose at >307°C (DTA / TG), soluble in water, λ max =392nm (aqueous solution).
[0125] Example 66: Weigh 10.0 g of potassium salt of hydroxyhemoglobin and stir and dissolve it in 200 ml of water. Separately, weigh 11.0 g of manganese sulfate and stir and dissolve it in 150 ml of water. Slowly mix the two solutions while stirring. Continue stirring for 1 hour and then let it stand overnight. Filter, wash with cold water, and dry under reduced pressure to obtain about 8.12 g of manganese salt of hydroxyhemoglobin as a dark brown solid. Decompose at >322°C (DTA / TG), slightly soluble in water, λ max =390nm (aqueous solution).
[0126] Example 67: Weigh 10.0 g of potassium salt of hydroxyhemoglobin and stir and dissolve it in 200 ml of water. Separately, weigh 14.0 g of ferrous sulfate and stir and dissolve it in 150 ml of water. Slowly mix the two solutions while stirring. Continue stirring for 1 hour and then let it stand overnight. Filter, wash with cold water, and dry under reduced pressure to obtain about 7.71 g of ferrous salt of hydroxyhemoglobin as a dark brown solid. Decompose at >331°C (DTA / TG), slightly soluble in water, λ max =371nm (aqueous solution).
[0127] Example 68: Weigh 10.0 g of potassium salt of hydroxyhemoglobin and stir and dissolve it in 200 ml of water. Separately, weigh 11.0 g of ferric chloride and stir and dissolve it in 120 ml of water. Slowly mix the two solutions while stirring, continue stirring for 1 hour, then let stand overnight, filter, wash with cold water, and dry under reduced pressure to obtain about 8.43 g of ferric salt of hydroxyhemoglobin as a dark brown solid. Decompose at >328°C (DTA / TG), slightly soluble in water, λ max =367nm (aqueous solution).
[0128] Example 69: Weigh 10.0 g of potassium salt of hydroxyhemoglobin and stir and dissolve it in 200 ml of water. Separately, weigh 14.0 g of zinc sulfate and stir and dissolve it in 150 ml of water. Slowly mix the two solutions while stirring. Continue stirring for 1 hour and then let it stand overnight. Filter, wash with cold water, and dry under reduced pressure to obtain about 8.94 g of zinc salt of hydroxyhemoglobin as a dark brown solid. Decompose at >303°C (DTA / TG), slightly soluble in water, λ max =375nm (aqueous solution).
[0129] Example 70: Weigh 10.0 g of potassium salt of hydroxyhemoglobin and stir and dissolve it in 200 ml of water. Separately, weigh 15.0 g of copper sulfate and stir and dissolve it in 150 ml of water. Slowly mix the two solutions while stirring. Continue stirring for 1 hour and then let it stand overnight. Filter, wash with cold water, and dry under reduced pressure to obtain about 8.22 g of copper salt of hydroxyhemoglobin as a dark brown solid. Decompose at >266°C (DTA / TG), slightly soluble in water, λ max =363nm (aqueous solution).
[0130] Example 71: 100.0 g of chlorin iron parent drug (produced by Nanjing Baxter Bioengineering Co., Ltd.) was weighed and dissolved in 1000 ml of 6% potassium hydroxide aqueous solution with stirring. The mixture was stirred in the dark for 5 hours. 8000 ml of acetone was slowly added. The mixture was stirred in the dark for 1 hour and then allowed to stand overnight. The mixture was filtered, washed with cold acetone, and dried under reduced pressure to obtain 9.02 g of potassium hydroxychlorophyllin iron salt, a dark green powder. It decomposed at >320°C (DTA / TG), was easily soluble in water, and had a λ max =395nm (aqueous solution).
[0131] Example 72: The same as Example 71, except that the sodium hydroxide aqueous solution was substituted for the potassium hydroxide solution, to obtain 8.46 g of sodium hydroxychlorophyllin iron salt, a dark green powder >311 ° C decomposition (DTA / TG), soluble in water, λ max =396nm (aqueous solution).
[0132] Example 73: 5.0 g of sodium ferric hydroxychlorophyllin was weighed and dissolved in 1000 ml of water. 5% sulfuric acid was slowly added dropwise while stirring in the dark until the pH was ≈ 4. The mixture was allowed to stand overnight, filtered, and the filter cake was washed with water until neutral. The solid was dried under reduced pressure. The solid was dissolved in 1000 ml of acetone. Dry ammonia was slowly introduced into the mixture while stirring until saturated. The mixture was allowed to stand overnight, filtered, washed with a small amount of cold acetone, and dried under reduced pressure to obtain 3.34 g of ammonium ferric hydroxychlorophyllin, a dark green powder. It decomposed at >255°C (DTA / TG), was easily soluble in water, and had a λ max =404nm (aqueous solution).
[0133] Example 74: 10.0 g of sodium ferric hydroxychlorophyllin was weighed and dissolved in 100 ml of water with stirring. Separately, 11.0 g of magnesium chloride hexahydrate was weighed and dissolved in 50 ml of water with stirring. The two solutions were slowly mixed with stirring at room temperature to produce a precipitate. The precipitate was stored in the dark overnight, filtered, washed twice with cold water, filtered, and dried under reduced pressure to obtain 7.27 g of magnesium ferric hydroxychlorophyllin as a dark green powder. It decomposed at >317°C (DTA / TG), was soluble in water, and had a λ max =401nm (aqueous solution).
[0134] Example 75: 10.0 g of sodium ferric hydroxychlorophyllin was weighed and dissolved in 100 ml of water with stirring. 10.0 g of calcium chloride dihydrate was weighed and dissolved in 50 ml of water with stirring. The two solutions were slowly mixed with stirring at room temperature to produce a precipitate. The precipitate was stored in the dark overnight, filtered, washed with cold water, filtered, and dried under reduced pressure to obtain 7.71 g of calcium ferric hydroxychlorophyllin as a dark green powder. It decomposed at >332°C (DTA / TG), was soluble in water, and had a λ max =402nm (aqueous solution).
[0135] Example 76: 10.0 g of sodium ferric hydroxychlorophyllin was weighed and dissolved in 110 ml of water with stirring. 10.0 g of ferrous chloride tetrahydrate was weighed and dissolved in 50 ml of water with stirring. The two solutions were slowly mixed with stirring at room temperature to produce a precipitate. The precipitate was stored in the dark overnight, filtered, washed with cold water, filtered, and dried under reduced pressure to obtain 9.26 g of ferrous hydroxychlorophyllin as a dark green powder. It decomposed at >315°C (DTA / TG), was slightly soluble in water, and had a λ max =398nm (aqueous solution).
[0136] Example 77: 10.0 g of sodium ferric hydroxychlorophyllin was weighed and dissolved in 110 ml of water with stirring. Separately, 10.0 g of ferric chloride hexahydrate was weighed and dissolved in 50 ml of water with stirring. The two solutions were slowly mixed with stirring at room temperature to produce a precipitate. The precipitate was stored in the dark overnight, filtered, washed with cold water, filtered, and dried under reduced pressure to obtain 8.11 g of ferric hydroxychlorophyllin as a dark green powder. It decomposed at >304°C (DTA / TG), was slightly soluble in water, and had a λ max =401nm (aqueous solution).
[0137] Example 78: 10.0 g of sodium ferric hydroxychlorophyllin was weighed and dissolved in 100 ml of water with stirring. 10.0 g of manganese chloride tetrahydrate was weighed and dissolved in 50 ml of water with stirring. The two solutions were slowly mixed with stirring at room temperature to produce a precipitate. The precipitate was stored in the dark overnight, filtered, washed with cold water, filtered, and dried under reduced pressure to obtain 87.8 g of ferric manganese hydroxychlorophyllin as a dark green powder. It decomposed at >331°C (DTA / TG), was slightly soluble in water, and had a λ max =403nm (aqueous solution).
[0138] Example 79: 10.0 g of sodium ferric hydroxychlorophyllin was weighed and dissolved in 100 ml of water with stirring. Separately, 10.0 g of zinc chloride was weighed and dissolved in 50 ml of water with stirring. The two solutions were slowly mixed with stirring at room temperature to produce a precipitate. The precipitate was stored in the dark overnight, filtered, washed with cold water, filtered, and dried under reduced pressure to obtain 8.67 g of ferric zinc hydroxychlorophyllin as a dark green powder. It decomposed at >327°C (DTA / TG), was slightly soluble in water, and had a λ max =403nm (aqueous solution).
[0139] Example 80: 10.0 g of sodium iron hydroxychlorophyllin was weighed and dissolved in 100 ml of water with stirring. Separately, 9.0 g of copper chloride dihydrate was weighed and dissolved in 50 ml of water with stirring. The two solutions were slowly mixed with stirring at room temperature to produce a precipitate. The precipitate was stored in the dark overnight, filtered, washed with cold water, filtered, and dried under reduced pressure to obtain 8.42 g of copper iron hydroxychlorophyllin as a dark green powder. It decomposed at >264°C (DTA / TG), was slightly soluble in water, and had a λ max =395nm (aqueous solution).
[0140] Example 81: Differential Thermal Analysis / Thermogravimetric Analysis (DTA / TG) of Chlorin Iron Sodium Salt and Chlorin Iron
[0141] Testing instrument: Shimadzu DTG-60 differential thermal and thermogravimetric analyzer
[0142] Test samples: Chlorin iron sodium salt, Chlorin iron
[0143] Reference: Aluminum oxide
[0144] Test gas flow: nitrogen
[0145] Heating rate: 10℃ / min
[0146] Temperature range: 25℃~500℃
[0147] Sample weight: 4.3-4.5 mg
[0148] Analysis software: ta60WS Ver.2.11
[0149] Result analysis: The DTA / TG spectra of sodium chlorin iron salt and chlorin iron were tested and the two sample spectra were merged using analysis software. The results are shown in Figure 1, which are a sample DTA comparison chart (Figure 1: upper figure) and a TG comparison chart (Figure 1: lower figure), respectively.
[0150] As can be seen from the figure, the DTA / TG spectra of the samples after dihydrochlorin iron is converted into sodium salt show that both samples have no melting phase transition peak (no melting point), while the difference in thermal response is very obvious. Under the same range (uV), the DTA curve of acid-type dihydrochlorin iron (Figure 1: upper figure) is stable and has little fluctuation, and the endothermic peak / exothermic peak is almost flat, while the curve of dihydrochlorin iron sodium salt has large fluctuations. The test results show two large exothermic peaks at 271.67℃ and 453.24℃; 90.46℃ is the endothermic peak of the dehydration or removal of low-boiling-point small molecules of the dihydrochlorin iron sample, and 219.16℃ is the exothermic peak of the decomposition of the dihydrochlorin iron sample. The samples within the range are The specific heat of the samples did not change significantly (approximately horizontal line); the dehydration of sodium dihydrochlorin iron salt absorbed heat significantly, the endothermic peak moved to 71.7℃, and the amount of heat absorbed increased significantly. After 110℃, the specific heat of the sample increased, and the curve rose. It began to decompose at 180℃ and released heat violently to 271.67℃ where an exothermic peak appeared. A second exothermic peak appeared at 453.24℃. After further decomposition, the specific heat began to decrease. The thermal reaction difference between the two samples was very significant. The decomposition point of the salt sample was significantly higher than that of the acid sample. Comparison of the TG spectra (Figure 1: below) shows that the TG curve of dihydrochlorin iron changes slowly before 140°C, and the sample has a small weight loss of 3.256%, while the TG curve of dihydrochlorin iron sodium salt decreases rapidly, and the sample dehydrates and loses 7.511%, which is equivalent to the content of two molecules of hydration (salt); dihydrochlorin iron slowly loses weight (decomposes) after 180°C, and the weight loss accelerates (decomposition intensifies) at 390°C. Dihydrochlorin iron sodium salt begins to lose weight (decompose) significantly after 200°C, and the weight loss rate decreases at 295°C, and the weight loss rate increases again after 405°C (decomposition intensifies), indicating that the decomposition temperature of the salt sample is significantly higher than that of the acid sample.
[0151] The results show that the two samples have only decomposition points but no melting points when heated, and the thermal stability of dihydrochlorin iron salt is significantly stronger than that of the acid sample.
[0152] Example 82: Dilution and pH determination of sample solutions such as sodium chlorin iron salt
[0153] Sample: Sodium ferric chlorophyllin (commercially available food additive, food grade, content 96%), sodium protoporphyrin (commercially available pharmaceutical raw material, pharmaceutical grade, content 95.0%), sodium ferric chlorin (content determined by photometry: 95.5%, the same below), potassium hemoglobin (content 96.0%), magnesium ferric chlorophyllin (content 97.3%), magnesium hemoglobin (content 95.7%), purified water (pH = 7);
[0154] Instruments: FA1604N electronic balance, PHS-3C benchtop acidity meter, ultrasonic analyzer, volumetric flask;
[0155] Method: Accurately weigh 0.2500 g of sample and place it in a 25 ml volumetric flask. Dissolve it in purified water and dilute to the mark to prepare a 1.00% (10000.0 ppm) initial solution. Take a portion of the initial solution and dilute it with purified water at different ratios to prepare a series of solutions with concentrations ranging from 1000.0 to 0.1 ppm. Repeat the test three times for each sample to obtain its pH value. Prepare a solution of slightly soluble salt at a concentration below the saturated solubility, weigh an appropriate amount of sample, dissolve it, and dilute it in the same way for determination. The mol / L concentration corresponding to the ppm concentration and the solution pH determination results are shown in the table below:
[0156] The mol / L concentration and pH corresponding to different ppm concentrations of each sample solution
[0157]
[0158]
[0159] As shown in the table: for the tested samples, the solution pH of 1% soluble sodium / potassium salt (10000.0 ppm) reaches 10.21-10.95, indicating strong alkalinity. After being diluted tenfold, it still shows strong alkalinity. With further dilution, the pH decreases and the alkalinity decreases significantly. The pH of soluble magnesium salt (100 ppm) is similar to that of sodium / potassium salt solution. When the concentration reaches 30.0 ppm, the solution pH is <8.0 (pH=7.50-7.63), at which time the solution is in the pH range adapted to plant physiology. When diluted to 10.0 ppm, the solution is nearly neutral. Further dilution to the concentration of 1.0 ppm-0.1 ppm (-10 -6 mol / L) range, the sample solution unexpectedly showed weak acidity. Among the samples tested, chlorophyllin iron sodium salt (food additive) and protoporphyrin sodium (liver disease treatment drug) are both commercially available products. Like the newly prepared dihydrochlorin iron sodium salt and heme sodium salt samples of the present invention, their dilute solutions all showed unexpected weak acidity (not reported in the literature).
[0160] Generally speaking, the acid solution or alkaline solution is diluted to a concentration close to 10 -7 mol / L or more dilute concentration, the solution pH will be close to or approximately equal to 7.0, but will not exceed 7.0 (from acidic to alkaline, or from alkaline to acidic). Strong base and weak acid salt solution, under normal concentration conditions (concentration>>10 -7 mol / L) Due to the hydrolysis of weak acid radicals, the aqueous solution of its salt is obviously alkaline. After the solution is diluted, the hydrolysis effect of the salt gradually weakens as the concentration decreases. When it is diluted to 10 -6 ~10 -7mol / L (sample concentration in this example is 1.0 ppm to 0.1 ppm), the hydrogen ions provided by water dissociation gradually become dominant. At this time, the pH of the solution should be close to or approximately equal to 7.0. However, in this measurement, the pH is <7.0, and the solution unexpectedly changes from weak alkalinity to weak acidity. This result indicates the presence of acidic components in the system, that is, the porphin salt sample measured may contain a small amount / trace amount of coexisting acidic porphin. These residual acidic porphins are the main reason for the weak acidity of the solution after dilution.
[0161] Acidic porphine is a polybasic acid. For example, sodium protoporphyrin and heme are both dibasic acids. Dihydrochlorins and chelates are mixtures of monobasic, dibasic, and tribasic acid monomers. The soluble sodium, potassium, or ammonium salt samples used in the present invention are all prepared by a precipitation method in which the acidic porphine is neutralized with alkali in an organic solvent. Divalent and trivalent metal salts such as magnesium salts are prepared by a double decomposition precipitation method. During the salt formation reaction, various process factors such as component concentration, alkali addition rate, stirring uniformity, and reaction temperature restrict the formation of the precipitate and the composition of the product. Experiments have shown that during the preparation of porphine salts, salt formation is not complete, or a small amount of unreacted acidic molecules are simultaneously trapped by the precipitate, forming a coprecipitation phenomenon. In addition, the characteristic of planar porphine molecules that they easily aggregate with each other is the inherent reason for their easy induction of coprecipitation, making incomplete salt formation during the preparation inevitable. However, this unexpected pH change improves the practicality of the product of the present invention, making it more suitable for the physiological conditions of crops and more conducive to the application of field crops.
[0162] Example 83: Determination of light protection / light stability of sample solution
[0163] Samples: 90 samples of porphin salts and dihydrochlorin salts (content ≥95.0%, determined by photometry)
[0164] Reference substances: chlorin iron, hemin chloride
[0165] Instruments: Shimadzu UV2600 UV spectrophotometer, Xima AR813A illuminometer
[0166] Determination: Take an appropriate amount of salt sample and dissolve it in water to prepare a test solution with a concentration of ≈10ppm; for acid-type reference substance (extremely insoluble in water), prepare a test solution with a concentration of ≈10ppm using 30% to 50% ethanol aqueous solution.
[0167] After each test solution is prepared, the absorbance in the range of 200nm to 800nm (0 time) is scanned using an ultraviolet spectrophotometer. Each sample test solution is then divided into two portions. One portion is stored at room temperature at 25°C in the dark, and the other portion is placed under a light intensity of 30,000 lux. The solutions are taken at 1, 2, and 3 hours, respectively, and the scans are repeated to determine the absorbance of the test solution at each time point.
[0168] The absorbance value at the maximum absorption peak of each test solution at time 0 (start) was taken as 100% relative content, and the relative % content was calculated by comparing the absorbance value at each time point with the value at time 0.
[0169] Results: Under light-proof conditions, the contents of the tested salt samples and acid-type control samples remained basically unchanged, or slightly decreased in some cases (relative content still > 96.5%).
[0170] Comparative tests under light conditions show that the stability of salt sample solutions is significantly different from that of control samples. Taking the light stability of hemin and hemin magnesium salt solutions as an example, the absorbance scan comparison is shown in Figure 2: the relative content of hemin solution is reduced to less than 30% after 1 hour of light exposure, and only 20.21% after 3 hours. The corresponding relative content of hemin magnesium salt is 75.61% after 3 hours, which is much higher than the acid type control. The comparison of dihydrochlorin iron and its sodium salt also has similar results. The relative content changes of each comparative sample are shown in the table below.
[0171] Relative % content of sample solution under light-proof / light-exposed conditions for 3 hours
[0172]
[0173]
[0174] The time for the relative content of each sample solution to decrease by 50% under strong light conditions (half-life t 1 / 2 ), the results are shown in the following table:
[0175] Relative content half-life of sample solution under light-proof / light-exposed conditions t 1 / 2 (Hour)
[0176]
[0177] The results showed that under strong light, the half-life of the reference substances hemin and chlorin iron (t 1 / 2 ) were 0.69 hours and 0.73 hours, respectively, while the half-lives of its magnesium salt and sodium salt increased to 6.0 hours and 3.41 hours, respectively, an increase of 8.69 times and 4.67 times. The light stability of the salt compound solution was significantly enhanced compared with the acid control. Under light-shielded conditions, the sample salt compound solution t 1 / 2 It is also significantly longer than that of the acid compound solution, indicating that the salt compound has good stability, is more suitable for the complex application environment in the field, and has more practical value.
[0178] The stability of 90 aqueous salt-type compound solutions (measured concentration: 12ppm to 25ppm) was tested under strong light irradiation for 3 hours. The results are shown in the table below:
[0179] The relative concentration percentage change of a series of salt sample solutions after 1 to 3 hours of illumination
[0180]
[0181]
[0182] *: Relative content at 0 hours: 100%
[0183] The results show that the series of salt compounds of the present invention all exhibit strong stability. After 3 hours of illumination, the relative content of most sample solutions can still be maintained at more than 50%. The stability is significantly better than the currently used acid-type products, and thus can better meet the actual wide range of needs and have higher practical value.
[0184] Example 84: Effects of sodium chlorin iron salt, heme potassium, and protoporphyrin potassium on wheat germination and seedling growth
[0185] Test variety: Huaimai 35
[0186] Samples: sodium chlorin iron salt, potassium heme, potassium protoporphyrin, water control (CK)
[0187] Methods: Each treatment was replicated three times. For each sample, 50 seeds of uniform, plump grains were selected, disinfected with sodium hypochlorite for 5 minutes, rinsed with clean water, and placed in plastic boxes lined with 100g of sand. 25ml of the prepared sample solution was then added. The seeds were arranged neatly, covered, and incubated in a 25°C incubator. Germination was considered complete when the bud length exceeded half the seed diameter (long axis). Based on wheat growth, the number of seeds budding and germination was recorded daily. On the sixth day, ten wheat seedlings were randomly selected to measure root length, plant height, and root number. On the seventh day, root weight and aboveground weight were measured. All parameters were measured in triplicate.
[0188] The wheat germination rates of the three samples with different concentrations are shown in Table 1 below:
[0189] Table 1 Wheat germination rate of each sample concentration
[0190]
[0191] The results showed that compared with the control (CK=0ppm), all samples in the concentration range of 0.2500ppm to 0.0025ppm showed a significant effect in promoting wheat germination, among which 0.2500ppm heme potassium had the best effect in promoting germination rate, and the other samples with a concentration of 0.0250ppm were even better.
[0192] The effects of different concentrations of sodium chlorin iron salt solutions on wheat seedling roots / seedlings are shown in Table 2 below:
[0193] Table 2 Effects of sodium chlorin iron salt on the growth of wheat seedlings
[0194]
[0195] The results showed that sodium dihydrochlorin iron salt had different effects on the growth of early wheat seedlings. It had a significant effect on promoting the growth of the root system, while the effect on the above-ground seedlings was relatively weak. 0.0250 ppm was a suitable concentration for use.
[0196] The effects of different concentrations of potassium hemin solution on wheat seedling roots / seedlings are shown in Table 3 below:
[0197] Table 3 Effects of different concentrations of heme potassium on the growth of wheat seedlings
[0198]
[0199]
[0200] The results showed that low concentrations of heme potassium (0.0250ppm or 0.0025ppm) could significantly promote the growth of the aboveground part of wheat seedlings and increase the number of roots, while the effect on promoting root length was weaker.
[0201] The effects of different concentrations of potassium protoporphyrin solution on wheat seedling roots / seedlings are shown in Table 4 below:
[0202] Table 4 Effects of different concentrations of protoporphyrin potassium on the growth of wheat seedlings
[0203]
[0204] The results showed that low concentrations of potassium protoporphyrin (0.0250 ppm or 0.0025 ppm) had a certain effect on promoting the growth of wheat roots, but had a weaker effect on the growth of the aboveground parts during the seedling stage.
[0205] Example 85: In vitro chlorophyllase inhibition activity test According to the literature method (Northwest Botanical Journal, 2003, 23 (5): 750-754.), 2.00 g of acetone powder prepared from mung bean leaves was accurately weighed and extracted with 50 mL of phosphate buffer (pH 7.0-7.3) for 4.0 h. After centrifugation at 4°C-5°C for 10 min, the supernatant with an active enzyme concentration of 0.13 mmol / L was used as the chlorophyllase solution. Dihydrochlorin salt samples with a concentration of 0.3 ppm to 30.0 ppm were added to the enzyme solution, and then the substrate chlorophyll (120 ppm) was added. The chlorophyllase inhibition rate of each salt sample solution was measured, and the chlorophyllase inhibition activity IC of the salt sample was calculated. 50 The results are shown in the following table:
[0206] Chlorophyllase inhibitory activity IC of a series of salt samples 50
[0207]
[0208]
[0209] Chlorin salts retain the strong chlorophyllase inhibitory activity of acidic chlorin, and are of great significance and value for practical applications.
[0210] Example 86: Experiment on inducing adventitious roots of mung bean hypocotyls
[0211] Preparation of test solution: Take 8 ml of commercially available STANLEY universal hydroponic nutrient solution and dilute it to 3200 ml with tap water (diluted 400 times) to obtain a dilute nutrient solution; weigh an appropriate amount of salt samples such as sodium protoporphyrin and potassium hemin, and use the dilute nutrient solution to prepare 0.010ppm and 0.1ppm sample test solutions, taking 150 ml of each; another 150 ml of the dilute nutrient solution is taken as a blank control. The test solution and control solution are placed in a brown bottle and covered with a black film. Select mung bean seedlings with uniform growth and a seedling height of 7 to 8 cm. Cut them 3 cm below the first true leaf node, and insert 8 mung bean seedlings (without roots) into each bottle so that the lower radicle is immersed in the solution. The room temperature is 20-25℃, and the solution is replaced every 2 days for a total of 7 days. Obvious differences will appear on the 2nd to 3rd day of treatment. Observe and measure on the 7th day, and calculate the average number of adventitious roots and the average total length of adventitious roots per cutting. The results are shown in the table below:
[0212]
[0213] The results showed that compared with the blank control, all the test samples had a significant effect on promoting the rooting range and number of mung bean hypocotyls, and the effects were better than the existing plant growth regulator product hemin chloride.
[0214] Example 87: Experiment on Controlling Sheath Blight and Increasing Rice Yield (Application of Plant Immune Inducers)
[0215] Location: Zhonghua Family Farm, Guangming Village, Dazhong Street, Dafeng District, Jiangsu Province. A 6-mu field with flat terrain and good fertility of clay loam was selected, and the previous crop was wheat.
[0216] Experimental rice varieties: Nanjing 9108,
[0217] The seeds were sown on May 16, 2021 and transplanted on June 12, 2021. The plant spacing was 18 cm and the row spacing was 25 cm.
[0218] According to the field efficacy criteria of GB / T17980.20-2000, two treatments were set: treatment 1: sodium chlorin iron salt 3.0 mg / mu, and treatment 2: clean water (control). In combination with plant growth characteristics and pest control needs, the pesticide was sprayed once at the end of tillering (July 22, 2021), the jointing and booting stage (August 16, 2021), and the full heading stage (August 30, 2021). The water consumption per mu was 30 liters, 45 liters, and 45 liters, respectively (concentrations: 0.100 ppm, 0.067 ppm, and 0.067 ppm). The test samples were dissolved, diluted, and stirred evenly before application. Each treatment area was 3 mu.
[0219] Before harvest, samples were taken from five points in each treatment (20 m 2 ) Detailed inspection of rice sheath blight condition, and the correction control effect is as follows:
[0220]
[0221] The harvest time was November 8, 2021. Before the harvest, the yield composition and structure were investigated, and then the per-acre yield was measured. The results are as follows:
[0222]
[0223] The experiment shows that sodium dihydrochlorin iron salt has obvious effects in preventing and treating rice sheath blight, and also has a good effect on increasing rice yield. It is a plant immune inducer with good performance.
[0224] Example 88: Experiment on Controlling Rice Leaf Blast and Increasing Yield (Application of Plant Immune Inducers)
[0225] Location: Zhonghua Family Farm, Guangming Village, Dazhong Street, Dafeng District, Jiangsu Province, previous crop rapeseed.
[0226] Test plot: flat terrain, clay loam, good fertility;
[0227] Rice variety: Nanjing 9108;
[0228] The seeds were sown on May 16, 2021 and transplanted on June 14, 2021. The plant spacing was 18 cm and the row spacing was 25 cm.
[0229] The experiment was carried out in accordance with the field efficacy guidelines GB / T17980.19-2000 experimental specifications. There were two treatments in the experiment, treatment 1: sodium chlorin iron salt, treatment 2: blank control (water), which were fully diluted and dissolved before application. In combination with the characteristics of pest and disease control, the pesticide was applied once at the end of tillering (July 22, 2021), the jointing and heading stage (August 16, 2021), and the full heading stage (August 30, 2021). The application rate was 3 mg / mu of sodium chlorin iron salt, and the water consumption per mu was 30L, 45L and 45L respectively (sample concentrations: 0.1ppm, 0.067ppm and 0.067ppm). The area of each treatment was 3 mu. According to the five-point sampling method, 5 sampling points were set for each treatment (20m 2 The occurrence of rice leaf blast was investigated in the field before harvest, and the corrected control effect is shown in the following table:
[0230]
[0231] The experimental results show that sodium dihydrochlorin iron salt can significantly enhance the resistance of rice to rice leaf blast and has the application effect of plant immune inducer.
[0232] The harvest time was November 8, 202. Before the harvest, the yield composition was investigated and the yield per mu was measured. The sample had a significant yield increase effect. The specific results are shown in the following table:
[0233]
[0234] Example 89: Experiment on increasing pepper yield by spraying heme potassium salt solution
[0235] Experimental location: Litangfang Village, Wucheng Town, Wucheng County, Dezhou City,
[0236] Experimental site: medium loam, medium to high fertility, previous crop: sorghum.
[0237] Experimental variety: Hebei Jize pepper; planting density: 3500 trees / mu;
[0238] Planting method: mechanical transplanting;
[0239] Planting time: May 8, 2020;
[0240] Test method: The test and control areas were 10 mu each. The treatment group was sprayed with potassium hemoglobin solution, the control group was sprayed with hemoglobin (the dosage concentration was the same as that of the treatment group), and the blank was sprayed with water. The treatment group and the control were sprayed on May 19 (after transplanting) and July 2 (blooming period), respectively. The dosage was 1.5 mg / mu, and the water consumption per mu was 15L and 30L respectively (sample concentration: 0.1ppm and 0.05ppm). On September 13, a sampling survey was conducted, and ten pepper plants with uniform growth were selected from the treatment group and the control group respectively. The number of fruits and the weight of single fruit were counted; the whole field was harvested three times on August 30, September 13, and September 25. The yield was combined and statistically compared, and the results are as follows:
[0241]
[0242] The experiment showed that spraying peppers with hemoglobin potassium salt can significantly increase the fruit setting rate and single fruit weight, and has a significant yield-increasing effect. The hemoglobin in the control group also has a good yield-increasing effect, but the yield increase is not as good as hemoglobin potassium salt, and the difference is obvious.
[0243] Example 90: Experiment on increasing yield of tomatoes by spraying sodium iron chlorophyllin
[0244] Experimental location: Plot of the 3rd Company of the 22nd Regiment of Xinjiang Production and Construction Corps, previous crop nursery, light soil texture.
[0245] Variety: Processing Tomato 1615;
[0246] Cultivation methods employed flat planting, mulching, seedling transplanting, and pressurized drip irrigation. Seedlings were transplanted on April 29th, with a planting density of 2,600 plants per mu. The control and treatment areas each covered 20 mu. The treatment area was sprayed twice, at the beginning of flowering (May 22, 2021) and at the fruit set stage (June 5, 2021), with a sodium iron chlorophyllin solution at a concentration of 0.05 ppm.
[0247] The harvest was on August 3. At harvest time, 5 consecutive plants were randomly selected from each treatment for sampling and statistics. The data are as follows:
[0248]
[0249] The results showed that sodium iron chlorophyllin can increase the fruit setting rate and single fruit weight of tomatoes, thereby increasing the per-acre yield of tomatoes by more than 27%; it was also observed that after spraying sodium iron chlorophyllin, the red-to-green fruit ratio of tomatoes reached 3.36 (control: red-to-green fruit ratio 3.17), and the red-to-green fruit ratio increased by 5.91%, indicating that sodium iron chlorophyllin can not only increase yield, but also has the effect of promoting early coloring of tomatoes and improving the quality of fruits and vegetables. The experiment proved that sodium iron chlorophyllin has high practical value and broad application prospects.
[0250] Example 91: Comparative Study on Spraying Wheat Yield Increase by Using Dihydrochlorin Iron and Its Potassium Salt
[0251] Experimental location: Wheat experimental field of the Agricultural Science Institute of Huanghai Farm, Jiangsu Province, previous crop:
[0252] Sowing time: December 10, 2020, sowing amount: 30kg / mu; rice;
[0253] Crops: Huaimai No. 35, 7 mu each of the chlorin iron (powder) treatment field, the potassium salt treatment field, and the control field (sprayed with water);
[0254] Methods: Spray the dihydrochlorin iron / potassium salt solution once at the three-leaf and one-heart stage (March 14, 2021), the booting stage (April 14, 2021), and the flowering stage (May 1, 2021). The dosage of dihydrochlorin iron / potassium salt each time was 3 mg / mu, and the water consumption per mu was 15 L, 30 L, and 30 L, respectively (concentrations: 0.2 ppm, 0.1 ppm, and 0.1 ppm).
[0255] The entire field was harvested on June 11, 2021. The yield data is as follows:
[0256]
[0257] Spraying 3 mg / mu of dihydrochlorin iron and its potassium salt both had a significant yield-increasing effect, but the potassium salt had a better yield-increasing effect.
[0258] Example 92: Experiment on spraying sodium chlorin iron to control tobacco diseases
[0259] Location: Wujiang Village, Tianwen Town, Weng'an County, Guizhou Province;
[0260] Variety: Yunyan 87, transplanted on May 13, row spacing 100 cm, plant spacing 50 cm
[0261] Samples: sodium chlorin iron salt, chlorin iron powder (positive control), lentinan aqueous solution (positive control), water (blank control)
[0262] Methods: Six treatments were set up, treatments 1-3: 3 different concentrations of sodium chlorin iron salt solutions; control 1: chlorin iron powder solution; control 2: 0.5% lentinan aqueous solution; control 3: blank control;
[0263] For each treatment, four relatively dispersed plots of 50 square meters were selected in the field. The tobacco leaves were sprayed twice on May 28 and June 4 during the root extension period (12-14 leaves) after transplanting. The spray volume for each treatment was the same (30 liters / mu). During the operation, the leaves were sprayed evenly without leaving any dead corners.
[0264] On July 15, we surveyed all tobacco plants in each treatment area and conducted a disease classification survey according to the national tobacco disease classification standard GB / T23222-2008. We also calculated the incidence rate and disease index of each treatment area. The results are as follows:
[0265] Spraying of sodium chlorin iron to control tobacco diseases
[0266]
[0267] The results showed that sodium dihydrochlorin iron salt significantly improved tobacco immunity, played a role in resisting tobacco mosaic virus and reducing the incidence rate, and the effect was better than the positive control dihydrochlorin iron and lentinan.
[0268] Example 93: Experiment on Spraying Tobacco with Sodium Chlorin Iron to Promote Yield Increase
[0269] Experimental location: Yutang Village, Huanghua Town, Changsha County, Hunan Province;
[0270] Variety: Yunyan 87, planting density 16,500 plants / hectare, plant spacing 50 cm, row spacing 110-120 cm
[0271] Method: Four spray concentrations were set, each with four plots of 20 square meters each. The pesticide was applied twice on May 8, 2019, during the rooting period (12 to 14 leaves) after tobacco leaves were transplanted. The water consumption per mu was 45 liters (spray volume: 1.35 liters / plot).
[0272] At harvest time, sampling was performed to calculate plant height, leaf length, width, and single leaf weight. All leaves in the plot were cured into flue-cured tobacco. The growth and yield of the flue-cured tobacco after spraying with each sample (sodium chlorin iron salt) were calculated. The results are shown in the following table:
[0273]
[0274]
[0275] There is a certain relationship between the effect of spraying sodium dihydrochlorin iron salt on tobacco leaves and its concentration. Under the experimental concentration, sodium dihydrochlorin iron salt can significantly increase the weight of single tobacco leaves, increase the width and length of leaves, and increase the per mu yield of tobacco, but 0.1ppm is more suitable and more conducive to increasing tobacco leaf yield.
[0276] Example 94: Experiment on spraying cotton with sodium iron chlorophyllin to control Verticillium wilt
[0277] Experimental location: Dongfanghong No. 1 Team, Wutubulag Town, Bole City, Xinjiang Uygur Autonomous Region, previous crop cotton;
[0278] Cotton variety: Xinluzhong 66, sown on April 21, 2020, one film and four rows, 15,000 plants per mu, and each treatment area was 1 mu.
[0279] Samples: Sodium ferric chlorophyllin, Bihu (positive control), water (blank control)
[0280] Method: Three sample concentrations were set, along with a positive control and a blank control, for a total of five treatments. The cotton was sprayed once at the seedling stage (May 28) and once at the bud stage (June 28), with the concentration adjusted each time. The concentration changes of sodium ferric chlorophyllin and the control (treatments 1-5) are shown in the following table:
[0281]
[0282] The incidence of Verticillium wilt was investigated 20 days after each sample application. Three survey points were selected for each treatment, with 100 plants selected at each point. The results of the investigation on the control effect are as follows:
[0283]
[0284]
[0285] The harvest time was November 15, 2020. During the harvest, three sampling points were selected in each treatment area. Each sampling point had an area of 0.01 mu. The cotton growth was recorded, and then the cotton was harvested and the yield increase rate was calculated. The data are as follows:
[0286]
[0287] The results showed that sodium iron chlorophyllin could significantly reduce the incidence of cotton wilt and increase cotton yield. As the spraying concentration of seedling samples increased, the effect of preventing and controlling cotton wilt became better. Compared with the positive control, the overall effect was better.
[0288] Example 95: Effect of chlorin iron potassium salt on germination of salt-stressed rice
[0289] This experiment set up three NaCl concentrations of 0, 2.5, and 4.5 g / L plus 0.2 ppm dihydrochlorin potassium salt, and a salt stress blank control (CK: 4.5 g / L NaCl solution), for a total of four treatments: (1) 4.5 g / L NaCl solution (CK); (2) 0 g / L NaCl solution-0.2 ppm dihydrochlorin potassium salt solution; (3) 2.5 g / L NaCl solution-0.2 ppm dihydrochlorin potassium salt solution; (4) 4.5 g / L NaCl solution-0.2 ppm dihydrochlorin potassium salt solution.
[0290] The selected rice seeds with full grains (variety: Nanjing 9108) were soaked in sodium hypochlorite solution for 2-3 minutes for disinfection, and then rinsed with clean water two to three times. After washing, 50 full seeds were selected and placed in the prepared soaking solution so that the seeds were completely immersed, and soaked at 25°C for 48 hours. After soaking, they were moved to a plastic box with two layers of paper towels laid flat, and the germination bed was moistened with the salt concentration solution corresponding to each treatment. The seeds were cultured in a constant temperature incubator at 25°C, with the lighting set to 12h light / 12h dark and 70% humidity. The germination bed was kept moist during the culture period. The rice seed germination and seedling growth were observed and recorded daily. The germination rate of each treatment was recorded on the 7th day. The number of normal seedlings was counted on the 14th day. Ten seeds were randomly selected from each treatment to measure the seedling length, root length, number of roots, root weight and seedling weight. The germination potential was counted on the 5th day of germination and the germination rate was counted on the 14th day. The results are as follows:
[0291] Table 1: Effects of sample solutions on rice germination under different salt stress concentrations
[0292]
[0293] Table 2: Effects of sample solutions on rice roots under different salt stress concentrations
[0294]
[0295] Table 3: Effects of sample solutions under different concentrations of salt stress on rice seedling growth
[0296]
[0297] Table 4: Effects of sample solutions on rice root-to-shoot ratio and seedling promotion rate under different salt stress concentrations
[0298]
[0299] The results showed that dihydrochlorin iron potassium salt exhibited good stress resistance, could promote the germination of salt-stressed rice seeds, improve the germination rate and vitality, promote the rooting of seedlings and the growth of the aboveground parts of plants, increase root length, promote the increase of seedling weight and root weight, and could significantly reduce the harm of salt stress to plants.
[0300] Example 96: Experiment on Spraying Sodium Ferric Chlorophyllin on Flooded Rice
[0301] Location: Xiaosijiao Village, Gushu Town, Dangtu County, Ma'anshan City, Anhui Province, irrigated land by the river;
[0302] Rice variety: Nanjing 9108
[0303] Flooding situation: On July 10, 2021, an area of 20 mu was flooded. The water receded on July 20. In ten days, the whole plant was submerged for nearly four days, and most of the plant was submerged for nearly six days. After the water receded, the rice plants became weak and the leaves turned yellow and drooped.
[0304] Method and dosage: Use aerial spraying to apply 10.0ppm sodium iron chlorophyllin solution, spraying 10 mu, average dosage 1.2L / mu (application rate: 12.0 mg / mu); blank control field 10 mu (0 mg / mu);
[0305] Results: On October 20, 2021, the control field harvested 320 jin / mu (moisture content 16.5%), and the treated field harvested 720 jin / mu (moisture content 16.5%). The spraying effect of sodium iron chlorophyllin was extremely significant.
[0306] Example 97: Experiment on spraying chlorin iron potassium salt on drought-resistant rice seedlings
[0307] Sample: potassium iron salt of chlorin, water (control)
[0308] Variety: Huiliangyou 473 rice variety
[0309] Method: Select plump rice seeds, disinfect them with 6% sodium hypochlorite for 2-3 minutes, and rinse them with water. Soak the seeds in clean water at room temperature (30±1℃) until they turn white. Move the seeds to seedling trays for seedling cultivation. After about 15 days, select rice seedlings with consistent growth and move them to buckets for further growth, with 3 holes per bucket and 2 plants per hole. The soil used is clay loam. Before transplanting, the soil is crushed, sieved, and mixed. The bucket is 30 cm high and the inner diameter of the bucket is 30 cm. Water, fertilizer, diseases and pests are all managed uniformly during the potting period of the seedlings. The dihydrochlorin iron potassium salt sample is prepared into two concentration solutions and sprayed on the transplanted rice seedlings.
[0310] Drought model: Transplanting began on August 18, 2020. The next day (September 19), rice seedlings were subjected to natural drought and sample spraying treatments. Soil moisture content was measured using the NY / T 52-1987 method. The specific plan and drought model results are shown in Table 1 below:
[0311] Table 1: Experimental factors and levels of rice drought stress
[0312]
[0313] As shown in the table: After natural drought, the soil moisture content changes from normal on day 0 (moisture content 26.0%) to mild drought (moisture content 6.0% to 10.0%) on the 3rd day, and worsens to moderate drought (moisture content 6.0% to 8.0%) on the 6th day.
[0314] After drought stress and sample spraying began at the rice tillering stage (September 19), the chlorophyll content (mg / g) of the leaves was measured twice, on the 3rd and 6th days (September 21 and September 25). The results are shown in Table 2 below:
[0315] Table 2: Chlorophyll content and changes in rice leaves under simulated drought conditions
[0316]
[0317] The results showed that under drought conditions, the chlorophyll content of rice leaves gradually decreased over time (blank treatment). Drought had a significant impact on the changes in chlorophyll content in rice leaves. However, after treatment with potassium chlorin iron solution, the chlorophyll content in rice leaves increased instead of decreased over time, proving that the sample could maintain the chlorophyll content under drought stress, delay the decomposition of chlorophyll, and have a significant anti-stress effect.
[0318] Example 98: In vitro experiment on the induction of plant resistance to pepper blight by sodium chlorin iron salt
[0319] Experimental method: The leaves of Nicotiana benthamiana were treated with sterile ultrapure water (DDW), 20.0ppm sodium dihydrochlorin iron salt and 2.0ppm sodium dihydrochlorin iron salt by injection. Then, the leaves were inoculated with the fungus cake of Phytophthora capsici LT263 7 days and 10 days later, and the results were observed 36 hours after inoculation.
[0320] Results: Compared with DDW treatment, 20.0ppm and 2.0ppm sodium chlorin iron salt treatment of N. benthamiana for 7 and 10 days could significantly reduce the lesion area of inoculated LT263.
[0321] Conclusion: Treatment of Nicotiana benthamiana with sodium ferric chlorin solution for 7 or 10 days can effectively weaken / reduce the infection of Phytophthora capsici.
[0322] Example 99: Potted experiment on the resistance of pepper to blight induced by sodium chlorin iron
[0323] Test culture medium
[0324] V8 medium: Add 1 g of CaCO3 to every 100 mL of V8 vegetable juice medium, centrifuge at 6000 rpm for 10 minutes, take the supernatant, dilute it 10-fold, add 15% agar powder, and sterilize at 121°C for 20 minutes.
[0325] Test seeds: Sujiao No. 5, bred by the Vegetable Research Institute of Jiangsu Academy of Agricultural Sciences.
[0326] Preparation of zoospores of Phytophthora capsici: Punch a disc from the edge of a freshly activated P. capsici plate. Use a needle to pick a 6 mm disc and transfer it to an empty 9 cm diameter Petri dish, facing upward. Ten discs are placed per dish. Add 15 mL of sterile water to the dish and place it in a clean bench under light, changing the water every 30 minutes for three times. Remove the remaining water with a pipette, then add 10 mL of V8 liquid medium. Incubate in a dark incubator at 25°C for 24 hours to induce the production of numerous cystospores. Place the dish in a 4°C refrigerator for 30 minutes, followed by another 30 minutes in a 25°C incubator to allow for the release of numerous zoospores. Collect 10 μL of the sample for microscopic observation and counting using a hemocytometer. Collect the remaining sample for later use.
[0327] Determination of the efficacy of sodium chlorin iron salt against pepper blight in potted plants
[0328] The experiment set up two treatments:
[0329] Control group (CK): water spray;
[0330] Treatment group: Spray of 2.0 ppm solution of sodium chlorin iron
[0331] Transplant pepper seedlings at the 4-6 leaf stage, plant one per pot, treat with sodium chlorin iron solution for 3 days, and then inoculate with pepper spores at an inoculum rate of about 1×10 5 Each treatment was repeated three times, with 18 pots in each repeat. After treatment, peppers were observed once a day, and the incidence rate, disease index and control efficiency were recorded.
[0332] According to the "Pepper Disease Survey and Forecasting Specification" (NY / T2060.1-2011), investigate the plant disease situation and calculate the incidence rate, disease index and control effect (Ye Minshuo et al., 2019):
[0333] Incidence rate = number of diseased plants / total number of plants × 100%
[0334] Disease index = [(number of diseased plants at each level × relative disease level) / (total number of plants surveyed × 5) × 100%
[0335] Control effect = [(control disease index - treatment disease index) / control disease index] × 100%
[0336] Extraction of total RNA from plants
[0337] 0.2 g of pepper leaves (samples) were collected for RNA extraction after treatment with sodium chlorin iron salt for 12, 24, 36, 48, 60, and 72 hours. RNA was extracted using the TRIzol method. Samples were placed in 2 mL centrifuge tubes, thoroughly ground with liquid nitrogen, and then 1 mL of TRIzol reagent (Thermo Fisher, USA) was added, mixed thoroughly, and allowed to stand for 5 minutes. 200 μL of chloroform was added, mixed thoroughly, allowed to stand for 5 minutes, and centrifuged at 12,000 g at 4°C for 15 minutes. The supernatant was transferred to a 1.5 mL centrifuge tube, an equal volume of pre-chilled isopropanol was added, mixed thoroughly, allowed to stand for 30 minutes, and centrifuged at 12,000 g at 4°C for 10 minutes. The supernatant was discarded, and the pellet was washed twice with 75% ethanol and centrifuged at 12,000 g at 4°C for 5 minutes. The supernatant was discarded, and the pellet was dissolved in 30 μL of 0.1% DEPC-treated water and stored at -80°C.
[0338] Synthesis of the first strand of cDNA and fluorescence quantitative PCR
[0339] First-strand cDNA The gDNA Removal and cDNA Synthesis SuperMix Kit (Quanshijin, Beijing) was used to synthesize the cDNA and remove residual genomic DNA from the RNA template. The total volume was 20 μL. 1000 ng of total RNA was supplemented with RNase-free water to 7 μL, and 1 μL of Random Primer (N9) was added for a total of 8 μL. After mixing, the mixture was incubated at 65°C for 5 minutes and placed on ice for 2 minutes. Then, 10 μL of 2× ES Reaction Mix was added. Mix 1 μL and gDNA Remover 1 μL; gently mix, incubate at 25°C for 10 min, then at 42°C for 15 min, inactivate by heating at 85°C for 5 s, and store at 4°C. Dilute cDNA 40-fold and store at -20°C until needed.
[0340] Real-time PCR was used to detect the expression of disease resistance-related genes PR1, WRKY40, WRKY53, ACCO, and GST in pepper leaves after treatment with sodium chlorin iron for different time periods. Actin was used as an internal reference. The specific primer sequences are shown in the table below:
[0341] Names and sequences of primers used in qRT-PCR
[0342]
[0343]
[0344] Using cDNA as template, ROCHE Amplification was performed on a 96 real-time fluorescence quantitative PCR instrument. The amplification system consisted of 10 μL of 2×PerfectStart™ Green Green qPCR SuperMix (Quanshijin, Beijing), 0.4 μL of upstream and downstream primers (10 μmol / L), 1 μL of cDNA, and 8.2 μL of Nuclease-free Water to a total volume of 20 μL. The reaction procedure was as follows: pre-denaturation at 95°C for 180 s; 40 cycles of 95°C for 10 s, 60°C for 30 s; 95°C for 10 s, 65°C for 10 s, and 97°C for 1 s; and finally cooling at 37°C for 30 s. The specificity of the reaction system was determined by the melting curve and fluorescence value change curve. The experiment was repeated three times, and the relative expression of the genes was calculated using 2-ΔΔCt. The results are shown in the following table:
[0345]
[0346] The incidence of pepper blight was significantly reduced after treatment with sodium chlorin iron salt, with a control efficiency of 71.89%, indicating that sodium chlorin iron salt had a strong plant immune inducing activity even at a concentration of 2.0 ppm.
[0347] Example 100: Alleviating herbicide damage and significantly increasing rice yield
[0348] Location: Mahu Village, Xuyi County, Huai'an City, Jiangsu Province,
[0349] Rice variety: Jinjing 818 rice,
[0350] Sample: Sodium chlorin iron salt (0.25 ppm aqueous solution)
[0351] Time: June-November 2021
[0352] Plot conditions: previous wheat crop, consistent soil fertility, and same field management.
[0353] Method: 1.5 mu of treatment field and 1.5 mu of control field were set up respectively; after the rice was sprayed with herbicide and showed phytotoxicity, the sample was sprayed twice, and a blank control with clean water was attached. The specific operation is as follows:
[0354] On June 20, when the weeds had 3 leaves and the rice had 3-3.5 leaves, both the treated and control fields were sprayed with 4% imazamox 200 ml / mu + 10% pyrifoxitin 40 ml / mu stem and leaf spraying, using 30 kg of water per mu; one week later, the weed control effect was good, but the rice showed obvious phytotoxicity; 10 days after the herbicide application (June 30), the treated fields were sprayed with 7.5 mg / mu of the sample, using 30 liters of solution per mu; the control fields were sprayed with clean water; at the rice rupture stage (August 25), the fields were sprayed again using the same method.
[0355] Results: Harvested on November 10, the yield data is as follows:
[0356]
[0357] Field observations revealed significant weed control effects in rice fields, with no significant differences between the treated and control plots. However, some phytotoxic effects were observed, impacting crop growth. Rice growth in plots sprayed with the sodium chlorin iron solution outperformed the blank control, with significant increases in the number of ears per mu, number of grains per ear, and 1,000-grain weight. Yield also increased significantly, reaching over 22% per mu. This suggests that spraying the sodium chlorin iron solution not only has no impact on weed control but also significantly mitigates the adverse effects of the herbicide, increasing yield per mu.
Claims
1. Porphine salts, including salts of porphine compounds or salts of dihydrochlorin compounds.
2. The porphine salt according to claim 1, characterized in that The salt of the porphin compound includes a salt of protoporphyrin or a salt of a protoporphyrin chelate; the salt of the dihydrochlorin compound includes a salt of pheophorbide or a salt of a pheophorbide chelate.
3. The porphine salt according to claim 1, characterized in that The porphin compound is selected from protoporphyrin, hemin chloride or hydroxyhemoglobin; the dihydrochlorin compound is selected from pheophorbide, dihydrochlorin iron (ferric chloride chlorophyllin), hydroxychlorophyllin iron, chlorophyllin iron, chlorophyllin zinc or chlorophyllin copper.
4. The porphine salt according to claim 1, characterized in that The salt of the porphine compound is prepared by reacting acidic protoporphyrin or its chelate with metal ions to form a salt; the salt of the dihydrochlorin compound is prepared by reacting acidic pheophorbide or its chelate with metal ions to form a salt.
5. The porphine salt according to claim 1, characterized in that The salts of the porphin compounds include monovalent, divalent or trivalent metal ion salts of the porphin compounds; the salts of the dihydrochlorin compounds include monovalent, divalent or trivalent metal ion salts of the dihydrochlorin compounds.
6. The porphine salt according to claim 1, characterized in that The salts of the porphin compounds include sodium, potassium, ammonium, magnesium, calcium, ferrous, ferric, zinc, manganese or copper salts of the porphin compounds; the salts of the dihydrochlorin compounds include sodium, potassium, ammonium, magnesium, calcium, ferrous, ferric, zinc, manganese or copper salts of the dihydrochlorin compounds.
7. The porphine salt according to claim 1, characterized in that The porphine salt includes: Potassium, ammonium, magnesium, calcium, ferrous, ferric, zinc, manganese and copper salts of protoporphyrin, Sodium, potassium, ammonium, magnesium, calcium, ferrous, ferric, zinc, manganese, and copper salts of hemin, Potassium, ammonium, magnesium, calcium, ferrous, ferric, zinc, manganese and copper salts of hydroxyhemoglobin, Sodium, potassium, ammonium, magnesium, calcium, ferrous, ferric, zinc, manganese and copper salts of chlorin iron (ferric chlorophyllin chloride), Sodium, potassium, ammonium, magnesium, calcium, ferrous, ferric, zinc, manganese and copper salts of ferric hydroxychlorophyllin, Ammonium, ferrous, ferric, and copper salts of ferric chlorophyllin, Potassium, ammonium, magnesium, ferrous, ferric, zinc, manganese and copper salts of chlorin (pheophorbide), Potassium, ammonium, magnesium, calcium, ferrous, iron, zinc, manganese and copper salts of zinc chlorophyllin, Ammonium, magnesium, calcium, ferrous, ferric, zinc, manganese and copper salts of copper chlorophyllin.
8. The method for preparing a porphine salt according to any one of claims 1 to 7, characterized in that: The method comprises reacting an acidic porphin compound or a dihydrochlorin compound with a monovalent metal hydroxide to form a precipitate, and separating to obtain a monovalent metal ion salt of the porphin compound or the dihydrochlorin compound; or reacting a monovalent metal salt of the porphin compound or the dihydrochlorin compound with a soluble polyvalent metal ion salt to form a precipitate, and separating to obtain a polyvalent metal ion salt of the porphin compound or the dihydrochlorin compound.
9. The method for preparing a porphine salt according to claim 8, wherein: The metal hydroxide is selected from sodium hydroxide, potassium hydroxide or ammonia; In the preparation process of the multivalent metal ion salt of the porphin compound or dihydrochlorin compound, the monovalent metal salt of the porphin compound or dihydrochlorin compound is selected from the sodium salt or potassium salt of the porphin compound or dihydrochlorin compound; the soluble multivalent metal ion salt includes sulfate, hydrochloride or nitrate of divalent or trivalent metal ion.
10. The method for preparing a porphine salt according to claim 8, wherein: The preparation method of the monovalent metal ion salt of the porphine compound or dihydrochlorin compound comprises the following steps: The acidic porphin compound or dihydrochlorin compound is prepared into a solution with an organic solvent, and then mixed with an organic solvent of a monovalent metal ion salt to precipitate; or the acidic porphin compound or dihydrochlorin compound and the monovalent metal ion salt are salted in an aqueous solution and then precipitated with an organic solvent; or the acidic porphin compound or dihydrochlorin compound is prepared into a solution with an organic solvent and then dry ammonia is introduced into the solution to form a precipitate, and finally filtered, washed, and dried to obtain the product. The preparation method of the multivalent metal ion salt of the porphine compound or dihydrochlorin compound comprises the following steps: The aqueous solution of the monovalent metal salt of the porphin compound or the dihydrochlorin compound is mixed with the aqueous solution of the soluble multivalent metal ion salt, precipitated, filtered, washed and dried to obtain the product.
11. Use of the porphin salt according to any one of claims 1 to 6 as a plant growth regulator or plant immunity inducer.
12. The use according to claim 11, characterized in that The porphine salt includes: Sodium, potassium, ammonium, magnesium, calcium, ferrous, ferric, zinc, manganese and copper salts of protoporphyrin, Sodium, potassium, ammonium, magnesium, calcium, ferrous, ferric, zinc, manganese, and copper salts of hemin, Sodium, potassium, ammonium, magnesium, calcium, ferrous, ferric, zinc, manganese and copper salts of hydroxyhemoglobin, Sodium, potassium, ammonium, magnesium, calcium, ferrous, ferric, zinc, manganese and copper salts of chlorin iron, Sodium, potassium, ammonium, magnesium, calcium, ferrous, ferric, zinc, manganese and copper salts of ferric hydroxychlorophyllin, Sodium, potassium, ammonium, magnesium, calcium, ferrous, ferric, zinc, manganese and copper salts of ferric chlorophyllin, Sodium, potassium, ammonium, magnesium, calcium, ferrous, ferric, zinc, manganese and copper salts of chlorins, Sodium, potassium, ammonium, magnesium, calcium, ferrous, iron, zinc, manganese and copper salts of zinc chlorophyllin, Sodium, potassium, ammonium, magnesium, calcium, ferrous, ferric, zinc, manganese and copper salts of copper chlorophyllin.
13. The use according to claim 11, characterized in that This includes spraying, applying, soaking seeds, aerial spraying, ear soaking, irrigation or broadcasting on plants that need to regulate their growth or enhance their stress resistance or the environment in which the plants grow, so as to achieve the purpose of regulating the growth of the plants or enhancing their stress resistance.
14. The use according to claim 11, characterized in that When applied, the concentration / content of the applied porphine salt is 0.001 ppm to 10 ppm.
15. The use according to claim 11, characterized in that When used for seed soaking and crop field irrigation, the concentration / content of the applied porphine salt is 0.001ppm to 0.1ppm; when used for crop foliage spraying, the concentration / content of the applied porphine salt is 0.01ppm to 10ppm.
16. The use according to claim 11, characterized in that The effects of the plant growth regulator include promoting seed germination, increasing germination rate, increasing root length, promoting root growth, enhancing plant immunity and stress resistance, accelerating seedling growth, increasing chlorophyll content, delaying plant premature aging, and increasing yield and improving quality.
17. The use according to claim 11, characterized in that The effects of the plant immune inducer include improving plant stress resistance and increasing crop yield.
18. Use of a composition comprising the porphin salt according to any one of claims 1 to 6 as a plant growth regulator or plant immunity inducer.
19. The use according to claim 18, characterized in that The porphine salt includes: Sodium, potassium, ammonium, magnesium, calcium, ferrous, ferric, zinc, manganese and copper salts of protoporphyrin, Sodium, potassium, ammonium, magnesium, calcium, ferrous, ferric, zinc, manganese, and copper salts of hemin, Sodium, potassium, ammonium, magnesium, calcium, ferrous, ferric, zinc, manganese and copper salts of hydroxyhemoglobin, Sodium, potassium, ammonium, magnesium, calcium, ferrous, ferric, zinc, manganese and copper salts of chlorin iron, Sodium, potassium, ammonium, magnesium, calcium, ferrous, ferric, zinc, manganese and copper salts of ferric hydroxychlorophyllin, Sodium, potassium, ammonium, magnesium, calcium, ferrous, ferric, zinc, manganese and copper salts of ferric chlorophyllin, Sodium, potassium, ammonium, magnesium, calcium, ferrous, ferric, zinc, manganese and copper salts of chlorins, Sodium, potassium, ammonium, magnesium, calcium, ferrous, iron, zinc, manganese and copper salts of zinc chlorophyllin, Sodium, potassium, ammonium, magnesium, calcium, ferrous, ferric, zinc, manganese and copper salts of copper chlorophyllin.
Citation Information
Patent Citations
Sodium protoporphyrin production and application
CN101259127A
Dihydroporphyrin iron(III) chelates with plant growth regulating activity and their application as plant growth regulators
CN102285992A
Macrocyclic tetrapyrrole compounds, compositions and methods for increasing abiotic stress resistance in plants
CN112203511A
The use of protoporphyrin ix derivatives to improve the health of plants
CN113677204A
Composition containing 5-aminolevulinic acid and chlorophyllin metal salt
CN114287438A